Thermally conductive sheet

By increasing adhesion on the surface of the thermally conductive layer of the thermally conductive sheet and controlling the amount of volatile components, the problem of the thermally conductive sheet reducing adhesion under high temperature conditions is solved, and more stable thermal conductivity is achieved.

CN120226144APending Publication Date: 2025-06-27SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480004131.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-25
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The adhesion of the existing heat conductor sheets is reduced under high temperature heating conditions, resulting in peeling problems with semiconductor chips or heat sinks.

Method used

Adhesiveness is improved by imparting adhesion on at least one surface of the thermally conductive layer of the heat conducting sheet, and the amount of volatile components is adjusted to be 2 mass ppm or more and 80 mass ppm or less at 150°C.

Benefits of technology

A heat conducting sheet that maintains high adhesion before and after high-temperature heating such as the reflow soldering process is realized, and stripping from the semiconductor chip or radiator is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120226144A_ABST
    Figure CN120226144A_ABST
Patent Text Reader

Abstract

Provided is a thermally conductive sheet which is provided with a thermally conductive layer that contains a polymer matrix and a thermally conductive filler, at least one surface of the thermally conductive sheet being adhesive, and which has a volatile component content of 2-80 ppm by mass (inclusive) as measured by thermal desorption GC-MS at 150 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat conductive sheet. Background Art

[0002] In recent years, with the high-density wiring of multilayer wiring boards, the high-density wiring relative to semiconductor packages, the increased mounting density of electronic components, and the increase in heat generation per unit area due to the high integration of semiconductor elements themselves, etc., it is expected to improve the heat dissipation performance of semiconductor packages. It is known that a semiconductor package dissipates heat by sandwiching a heat dissipation material between a heat generating body such as a semiconductor chip and a heat dissipation body also called a radiator and making them closely adhere. Conventionally, thermal grease has been widely used as the heat dissipation material disposed between a semiconductor chip and a radiator.

[0003] A semiconductor package is usually heated to a certain temperature or higher when in use, etc. Each component such as a substrate, a semiconductor chip, and a radiator may warp during heating due to different coefficients of thermal expansion. Recently, with the increase in the size of chips, due to the warping of the semiconductor chip, the gap between the semiconductor chip and the radiator becomes larger and larger, and the thermal grease cannot follow this warping, resulting in a bad situation such as the generation of a gap. Therefore, research is being conducted on using a heat conductive sheet instead of thermal grease.

[0004] For the heat conductive sheet used in the above applications, it is necessary to improve the heat dissipation performance while improving the followability to warping. The reason is that if the followability to surrounding components is lacking, it cannot follow the warping like thermal grease, and it may peel off from the semiconductor chip or the radiator.

[0005] On the other hand, conventionally, for a heat conductive sheet, an adhesive layer is sometimes formed on the sheet surface for the purpose of improving adhesiveness, etc. For example, Patent Document 1 discloses a heat conductive sheet having an adhesive layer formed on one surface by spraying an acrylic adhesive liquid and drying it in normal temperature air for 1 minute.

[0006] In addition, in the semiconductor inspection process for confirming the performance of a semiconductor package, a detection technique that improves the heat dissipation performance of the semiconductor package as the heat generation amount of the semiconductor package increases is also expected. In the semiconductor inspection process, a test head is pressed against the semiconductor package by means of a heat dissipation material to confirm the temperature of the semiconductor chip. As the heat dissipation material, it is necessary to be able to be reused, so research is being conducted on using a heat conductive sheet instead of thermal grease, but high conformity to the test head is required.

[0007] Prior Art Documents

[0008] Patent Documents

[0009] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2020-116874 Summary of the Invention

[0010] Problems to be Solved by the Invention

[0011] Semiconductor packages are generally manufactured through a reflow soldering process accompanied by high-temperature heating. Therefore, as a heat-conducting sheet configured between a semiconductor chip and a heat sink, it is sometimes necessary to maintain adhesion to adherends such as the semiconductor chip and the heat sink even after high-temperature heating.

[0012] The heat-conducting sheet having an adhesive layer formed under the conditions described in Patent Document 1 is considered to have improved initial adhesion to the adherend. However, when applied to uses such as the reflow soldering process that involves high-temperature heating, there is a problem that the adhesion at the interface between the heat-conducting sheet and the adherend decreases during high-temperature heating.

[0013] In addition, in the semiconductor inspection process, high adhesion to the test head is also required. However, for conventional heat-conducting sheets, due to insufficient adhesion during high-temperature heating, it is sometimes difficult to load them on the test head.

[0014] Therefore, an object of the present invention is to provide a heat-conducting sheet that can maintain high adhesion before and after high-temperature heating such as in the reflow soldering process.

[0015] Means for Solving the Problems

[0016] The present inventors studied the main reasons for the decrease in the adhesion of the heat-conducting sheet and found that trace volatile components remaining in the adhesive layer and the heat-conducting sheet volatilize during heating processes such as the reflow soldering process and the installation process before the reflow soldering process, generating bubbles, thereby reducing the adhesion at the interface between the heat-conducting sheet and the adherend. In addition, it was also thoroughly clarified that by making the volatile component a certain amount or more, the adhesion of the heat-conducting sheet to the adherend can be improved. Based on these understandings, it was found that by imparting adhesiveness to at least one surface of the heat-conducting layer constituting the heat-conducting sheet and adjusting the amount of volatile components when the heat-conducting sheet is heated at 150 °C to a specified range, the above problems can be solved.

[0017] That is, the present invention provides the following [1] to

[10] .

[0018] [1] A heat-conducting sheet comprising a heat-conducting layer containing a polymer matrix and a heat-conducting filler, and at least one surface being adhesive, wherein the amount of volatile components measured by thermal desorption GC-MS when the heat-conducting sheet is heated at 150 °C is 2 mass ppm or more and 80 mass ppm or less.

[0019] [2] The heat-conducting sheet according to [1], wherein the polymer matrix is an organopolysiloxane.

[0020] [3] The heat-conducting sheet according to [1] or [2], further comprising an adhesive layer on at least one surface of the heat-conducting layer.

[0021] [4] The heat-conducting sheet according to [3], wherein the adhesive layer is formed by spraying.

[0022] [5] The heat-conducting sheet according to [3] or [4], wherein the adhesive layer is an acrylic adhesive layer.

[0023] [6] The heat-conducting sheet according to [5], wherein the acrylic adhesive layer has reactive double bonds.

[0024] [7] The heat-conducting sheet according to any one of [1] to [6], wherein the adhesiveness disappears by heating at 260 °C for 3 minutes.

[0025] [8] The heat-conducting sheet according to any one of [1] to [7], wherein the amount of volatile components measured by thermal desorption GC-MS of the heat-conducting sheet at 260 °C is 2500 mass ppm or less.

[0026] [9] The heat-conducting sheet according to any one of [1] to [8], wherein the adhesive force measured by the adhesion test of at least one surface is 2 N or more.

[0027]

[10] A heat-conducting sheet, which has a heat-conducting layer containing a polymer matrix and a heat-conducting filler, at least one surface of the heat-conducting layer is adhesive, and the amount of volatile components measured by thermal desorption GC-MS of the heat-conducting sheet at 150 °C is 2 mass ppm or more and 80 mass ppm or less.

[0028] Advantages of the Invention

[0029] According to the present invention, a heat-conducting sheet that can maintain a high degree of adhesion before and after high-temperature heating such as in the reflow soldering process can be provided. Description of the Drawings

[0030] Figure 1 It is a schematic diagram showing an example of the method of installing the heat-conducting sheet. Detailed Description of the Invention

[0031] [Heat-Conducting Sheet]

[0032] The heat-conducting sheet of the present invention has a heat-conducting layer containing a polymer matrix and a heat-conducting filler, and at least one surface is adhesive. Hereinafter, the heat-conducting sheet will be described in detail.

[0033] (Amount of Volatile Components)

[0034] The amount of volatile components of the heat-conducting sheet of the present invention measured by thermal desorption GC-MS at 150°C (hereinafter, also simply referred to as "the amount of volatile components at 150°C") is 2 mass ppm or more and 80 mass ppm or less. When the amount of volatile components at 150°C is less than 2 mass ppm, the amount of volatile components in the adhesive and the heat-conducting sheet itself becomes too small, and the flexibility of the adhesive and its followability to the gap with the adherend become insufficient, so that the initial adhesion before high-temperature heating such as the reflow soldering process may be low. In addition, if the amount of volatile components at 150°C exceeds 80 mass ppm, the heat-conducting sheet will contain an excessive amount of volatile components. Therefore, due to the bubbles generated during high-temperature heating, the adhesion of the heat-conducting layer to the adherend may be reduced.

[0035] From the above considerations, the amount of volatile components at 150°C is preferably 3 mass ppm or more and 70 mass ppm or less, more preferably 4 mass ppm or more and 60 mass ppm or less.

[0036] For the heat-conducting sheet of the present invention, the amount of volatile components measured by thermal desorption GC-MS at 260°C (hereinafter, also referred to as "the amount of volatile components at 260°C") is preferably 2500 mass ppm or less. As described later, after high-temperature heating such as the reflow soldering process, the adhesion of the heat-conducting layer to the adherend sometimes increases, but by making the amount of volatile components at 260°C 2500 mass ppm or less, it is not easy to hinder the increase in adhesion due to volatile components. From this aspect, the amount of volatile components at 260°C is more preferably 2300 mass ppm or less, and further preferably 1800 mass ppm or less.

[0037] In addition, the amount of volatile components at 260°C is not particularly limited. From the aspect of setting the amount of volatile components at 150°C to a desired range, it is preferably 30 mass ppm or more, more preferably 50 mass ppm or more, further preferably 70 mass ppm or more, and still further preferably 100 mass ppm or more.

[0038] It should be noted that the amount of volatile components at 150°C and 260°C can be set to a desired range by adjusting the drying process, the unit area weight (areal weight) of the adhesive layer, the type of volatile components, the curing conditions, etc. described later. In addition, as the volatile components, for example, volatile substances such as alkoxysilane compounds described later, diluents such as organic solvents, etc. can be cited.

[0039] In addition, the detailed steps and measurement conditions of thermal desorption GC-MS are as described in the examples.

[0040] (Adhesion)

[0041] At least one surface of the heat-conducting sheet of the present invention is adhesive. The heat-conducting sheet may have adhesiveness on only one surface or on both surfaces. Additionally, as described later, the heat-conducting sheet may have an adhesive layer on at least one surface of the heat-conducting layer, or the heat-conducting layer may contain an adhesive, such that the surface of the heat-conducting layer has adhesiveness, thereby making the surface of the heat-conducting sheet adhesive. The adhesive force of at least one surface of the heat-conducting sheet, that is, of the heat-conducting layer, is preferably 2 N or more, more preferably 2.5 N or more, further preferably 3 N or more, and even more preferably 4 N or more. When the adhesive force is above the above lower limit value, it can be said to have good adhesiveness. Additionally, the above adhesive force is not particularly limited, and in practical use, for example, it is 10 N or less, preferably 9.5 N or less, and more preferably 9 N or less.

[0042] It should be noted that the above adhesive force is measured through a tackiness test, also known as a tackiness value, and its detailed steps are as described in the examples.

[0043] Additionally, for at least one surface of the heat-conducting sheet that is adhesive, it is preferred that the adhesiveness disappears by heating at 260 °C for 3 minutes. It should be noted that the "disappearance of adhesiveness" mentioned here means that when the heat-conducting sheet is bonded to the adherend and then heated at 260 °C for 3 minutes, at least one surface loses its tackiness due to curing or the like and has an adhesiveness that cannot peel the heat-conducting sheet from the adherend. By making the heat-conducting sheet have the property of disappearing adhesiveness, it can be hermetically bonded to the adherend with a high adhesive force after high-temperature heating without being peeled off.

[0044] It should be noted that whether the adhesiveness of the heat-conducting sheet disappears can be determined, for example, by the following method. That is, after heating the heat-conducting sheet at 260 °C for 3 minutes, the heat-conducting sheet is cooled to 23 °C, and when measuring the tackiness value in an environment of 23 °C, if it is 1.5 N or less, it can be determined that the adhesiveness has disappeared.

[0045] Additionally, in the present invention, there is no particular limitation, but in the case where the adhesive layer is an acrylic adhesive layer and has reactive double bonds as described later, it can have the property of disappearing adhesiveness by heating at 260 °C for 3 minutes.

[0046] In this case, the reactive double bonds react by heating, thereby making the adhesiveness disappear. However, if it comes into contact with the adherend at this time, it will form a chemical bond with the adherend as the reaction proceeds, thereby increasing the adhesive force with the adherend. Additionally, at the same time, the adhesive layer cures and the mechanical strength also increases. Therefore, it can be considered that during high-temperature heating in a reflow soldering process or the like, it is not likely to peel off from the adherend.

[0047] (Polymer matrix)

[0048] The polymer matrix is a matrix composed of organic polymers, which are organic polymers such as elastomers and rubbers. Preferably, it is a substance formed by curing a liquid polymer composition (curable polymer composition) composed of a mixed system of a main agent and a curing agent. For the curable polymer composition, for example, it can be composed of an uncrosslinked rubber and a crosslinking agent, and can also contain monomers, prepolymers, etc. and a curing agent, etc. In addition, the above curing reaction can be room temperature curing or heat curing.

[0049] The polymer matrix is preferably an organopolysiloxane. In the present invention, by using an organopolysiloxane, the cured polymer matrix can be made soft and the filling property of the heat-conducting filler can be made good. The organopolysiloxane is preferably silicone rubber. In addition, the organopolysiloxane is preferably a curable silicone, and more preferably an addition reaction type silicone.

[0050] In the case of an addition reaction type silicone, the curable polymer composition is composed of an alkenyl-containing organopolysiloxane (main agent) and a hydrogen organopolysiloxane (curing agent). For the polymer matrix, it is sufficient if it is formed by curing them. It is considered that if an addition reaction type silicone is used, the adhesion to the adherend is easily improved by high-temperature heating based on a reflow soldering process or the like.

[0051] As the rubber, in addition to silicone rubber, various synthetic rubbers can also be used. As specific examples, acrylic rubber, nitrile rubber, isoprene rubber, polyurethane rubber, ethylene-propylene rubber, styrene-butadiene rubber, butadiene rubber, fluororubber, butyl rubber, etc. can be listed. In the case of using these rubbers, the synthetic rubber can be crosslinked in the heat-conducting sheet or can remain uncrosslinked (i.e., uncured). The uncrosslinked rubber is mainly used for flow orientation.

[0052] In addition, in the case of crosslinking (i.e., curing), as described above, for the polymer matrix, it is sufficient if it is formed by curing a curable polymer composition composed of an uncrosslinked rubber and a crosslinking agent, and the uncrosslinked rubber is composed of these synthetic rubbers.

[0053] In addition, as the elastomer, thermoplastic elastomers such as polyester thermoplastic elastomers and polyurethane thermoplastic elastomers, and thermosetting elastomers formed by curing a liquid polymer composition of a mixed system composed of a main agent and a curing agent can also be used. For example, a polyurethane elastomer formed by curing a polymer composition containing a polymer having a hydroxyl group and an isocyanate can be exemplified.

[0054] In addition, the polymer composition used to form the polymer matrix can be composed of organic polymer monomers, or can be a mixture containing a plasticizer and a polymer dispersant in addition to organic polymers. The plasticizer is suitable for use in the case of using synthetic rubber. By containing the plasticizer, the flexibility of the polymer matrix before crosslinking can be improved. For example, in the case where the polymer matrix is an organopolysiloxane, silicone oil can be used as the plasticizer. In addition, as the polymer dispersant, for example, alkoxysiloxane compounds, siloxane compounds containing aromatic rings, and siloxane compounds having hydroxyl groups described below can be used. That is, the curable polymer composition can be composed of a main agent and a curing agent, or can contain a plasticizer and a polymer dispersant in the main agent and the curing agent. In addition, considering that the amount of volatile components will not become excessive and the viscosity of the composition is adjusted to be low so that it is easy to highly fill the heat conductive filler described below, it is particularly preferred that the curable polymer composition contains a main agent, a curing agent, and a polymer dispersant.

[0055] The alkoxysiloxane compound used as the polymer dispersant has two or more siloxane bonds (also called siloxane skeletons), and has a structure in which an alkoxy group is bonded to at least one silicon atom. The alkoxysiloxane compound has a structure in which an organic substituent is bonded to at least one silicon atom among the silicon atoms constituting the siloxane bond. For the alkoxysiloxane compound, by having an alkoxy group and an organic substituent, the compatibility with the organopolysiloxane constituting the curable polymer composition can be improved. The number of repeating units n of the siloxane skeleton is preferably 11 or more. The number of repeating units n of the siloxane skeleton (-Si-O-) is preferably 11 or more and 350 or less, more preferably 20 or more and 300 or less, further preferably 50 or more and 270 or less, and further preferably 100 or more and 250 or less. When the number of repeating units n of the above siloxane skeleton is above the above lower limit value, the compatibility with the organopolysiloxane forming the matrix is improved, and further the increase in volatile components can be suppressed. In addition, when the number of repeating units n of the above siloxane skeleton is below the above upper limit value, it is easy to adjust the viscosity of the composition to be low.

[0056] As the alkoxy group and the organic substituent possessed by the alkoxysiloxane compound, the groups exemplified in the description of the above alkoxysilane compound can be cited. Considering the compatibility with the organopolysiloxane constituting the curable polymer composition, it is preferred to have at least an alkyl group.

[0057] Examples of the alkoxysiloxane compound include methylmethoxysiloxane oligomer, methylphenylmethoxysiloxane oligomer, methylepoxymethoxysiloxane oligomer, methylmercaptomethoxysiloxane oligomer, and methacryloylmethoxysiloxane oligomer.

[0058] One or more alkoxysiloxane compounds can be used.

[0059] In addition, as a polymer dispersant, a siloxane compound containing an aromatic ring having a structure represented by the following formula (1) can also be used.

[0060]

[0061] In formula (1), each R1 is independently a group represented by A-B or a monovalent hydrocarbon group having 1 to 4 carbon atoms, and at least one of the plurality of R1s is a group represented by A-B. The above A is a divalent organic group bonded to a silicon atom. The above B has 3 or more and 6 or less conjugated aromatic six-membered rings. Among the atoms constituting the above A, when the atom bonded to the aromatic six-membered ring of the above B is designated as an α-position atom, the atom bonded to the α-position atom is designated as a β-position atom, and the atom bonded to the β-position atom and other than the α-position atom is designated as a γ-position atom, any one of the α-position atom, the β-position atom, and the γ-position atom is a heteroatom, and n is an integer of 1 or more. It should be noted that A may also have a heteroatom in a part other than the α-position atom, the β-position atom, and the γ-position atom.

[0062] Here, the heteroatom is not particularly limited, and examples thereof include an oxygen atom, a nitrogen atom, a sulfur atom, a boron atom, etc. Among them, from the viewpoint of effectively improving the fluidity of the polysiloxane phosphor, an oxygen atom is preferred.

[0063] The siloxane compound containing an aromatic ring having the structure represented by the above formula (1) has 3 or more and 6 or less conjugated aromatic six-membered rings, and has a part with a large conjugated system in the molecular structure. Therefore, the siloxane compound containing an aromatic ring has a high adsorption property due to π-π interaction with respect to the heat-conducting filler having π electrons, and thus it is easy to disperse the heat-conducting filler.

[0064] A is preferably a divalent organic group having 11 or less carbon atoms, more preferably a divalent organic group having 10 or less carbon atoms. In this way, a siloxane compound containing an aromatic ring with a certain amount or less of carbon atoms in A is likely to improve the dispersibility of the heat-conducting filler, and thus is preferred. In addition, the lower limit of the carbon atom number of A is not particularly limited, and A is preferably a divalent organic group having 4 or more carbon atoms.

[0065] In addition, as described above, A has a heteroatom, and thus becomes a structural unit containing a heteroatom. Examples of such a structural unit include an ether, an ester, an amide, a urethane, a thioether, a thioester, etc. Among them, from the viewpoints of improving the dispersibility in the heat-conducting filler and improving the fluidity, an ether or an ester is preferred, and an ether is more preferred, and a cyclic ether is particularly preferred. It should be noted that a cyclic ether refers to an ether having a structure in which the carbon of the cyclic hydrocarbon is replaced by an oxygen.

[0066] Furthermore, considering improving the dispersibility and fluidity of the thermal conductive filler, A preferably has a cyclic ether structure represented by the following formula (5-1) or an ester skeleton represented by the following formula (5-2).

[0067]

[0068] In formula (5-1), *1 and *2 are bonding positions, R4 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, preferably a hydrogen atom. The two R4s may be the same or different. R3 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, preferably a hydrocarbon group having 1 to 4 carbon atoms, more preferably a hydrocarbon group having 1 to 3 carbon atoms, and further preferably an ethyl group. R5 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, preferably a hydrogen atom. The oxygen atom in formula (5-1) is the above-mentioned β-position atom or γ-position atom, preferably the β-position atom.

[0069] In formula (5-2), *3 and *4 are bonding positions. The oxygen atom having the bonding position of *3 is the above-mentioned α-position atom, β-position atom or γ-position atom.

[0070] Among the above, A preferably has a skeleton represented by formula (5-1).

[0071] Furthermore, considering improving the dispersibility and fluidity of the thermal conductive filler, A is preferably any structure represented by the following formula (6) to formula (10), and more preferably any structure represented by the following formula (6) or formula (7).

[0072]

[0073] In formula (6) to formula (10), *5 is the bonding position bonded to the aromatic six-membered ring possessed by B, and *6 is the bonding position bonded to the silicon atom in formula (1).

[0074] B in formula (1) has 3 or more and 6 or less conjugated aromatic six-membered rings. Conjugation means that unsaturated bonds and single bonds are alternately connected in the molecular structure, causing stabilization brought about by the interaction of p orbitals, delocalization of electrons (distributed throughout the conjugated system), etc. It should be noted that 3 or more and 6 or less conjugated aromatic six-membered rings are included in the concept of the above-mentioned polycyclic aromatic structure.

[0075] When the number of aromatic six-membered rings is 6 or less, the fluidity of the siloxane compound containing an aromatic ring is improved. When the number of aromatic six-membered rings is 3 or more, the adsorption property with the thermal conductive filler is improved, and the dispersibility of the thermal conductive filler is improved.

[0076] Considering balancing the improvement of the adsorption property and fluidity with the thermal conductive filler, the number of aromatic six-membered rings is preferably 4 or more and 5 or less.

[0077] The three or more and six or less conjugated aromatic six-membered rings may be a condensed ring compound composed of three or more and six or less aromatic six-membered rings or a non-condensed ring compound, and a condensed ring compound is preferred. In this way, when B contains a condensed ring compound or B is a condensed ring compound, it is preferred in terms of further improving the adsorption property to the heat conductive filler and improving the dispersibility.

[0078] Examples of the condensed ring compound include anthracene, anthracene derivatives, phenanthrene, phenanthrene derivatives, triphenylene, triphenylene derivatives, pyrene, pyrene derivatives, tetracene, tetracene derivatives, picene, picene derivatives, perylene, perylene derivatives, pentaphene, pentaphene derivatives, hexaphene and hexaphene derivatives. Among them, pyrene, pyrene derivatives, perylene or perylene derivatives are preferred. Here, a derivative means a compound having a substituent. For example, an anthracene derivative means anthracene having a substituent, and the same applies to other derivatives.

[0079] When the condensed ring compound has a substituent, at least one of the hydrogen atoms constituting the condensed ring compound is substituted by a substituent. Examples of the substituent include an organic group having 1 to 10 carbon atoms.

[0080] In consideration of improving the fluidity of the aromatic ring-containing siloxane compound in the present invention, the condensed ring compound preferably does not have a substituent. Therefore, B is particularly preferably pyrene or perylene.

[0081] In addition, for the above-mentioned condensed ring compound, any carbon atom constituting the condensed ring may be bonded to the above-mentioned A.

[0082] In the present invention, for B, the above-mentioned substances can be adopted without particular limitation, and the preferred structure of B is as follows.

[0083]

[0084] In the above formulas (11) to (14), * is the bonding position bonded to A.

[0085] In the above formulas (11) to (14), any one of the compounds of formulas (11) to (13) is preferably used as the condensed ring compound, and among them, pyrene of formula (11) or perylene of formula (12) is more preferred, and pyrene of formula (11) is further preferred.

[0086] In formula (1), at least one R1 is the group represented by A-B, and the remaining R1s are hydrocarbon groups having 1 to 4 carbon atoms. In formula (1), among a plurality of R1s, the number of the groups represented by A-B is preferably 1 or more and 5 or less, more preferably 1 or 2, and the rest are monovalent hydrocarbon groups having 1 to 4 carbon atoms. When there are a plurality of groups represented by A-B, the plurality of groups represented by A-B may be the same or different.

[0087] Examples of the monovalent hydrocarbon group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, etc., and among them, a methyl group is preferred. In the case of having a plurality of monovalent hydrocarbon groups having 1 to 4 carbon atoms, the plurality of monovalent hydrocarbon groups having 1 to 4 carbon atoms may be the same or different.

[0088] In formula (1), n represents the number of repetitions of the siloxane skeleton, and n is an integer of 1 or more. There is no particular limitation as long as n is an integer of 1 or more, preferably 400 or less, more preferably 300 or less, still more preferably 250 or less, and preferably 10 or more, more preferably 40 or more, still more preferably 200 or more. When the number of repeating units n of the above siloxane skeleton is at least the above lower limit value, the compatibility with the organopolysiloxane forming the matrix is improved, and an increase in volatile components can be suppressed. In addition, when the number of repeating units n of the above siloxane skeleton is at most the above upper limit value, it is easy to adjust the viscosity of the composition to be low, and the fluidity becomes good.

[0089] (Siloxane compound having a hydroxyl group)

[0090] The above polymer dispersant may be a siloxane compound having a hydroxyl group. The siloxane compound having a hydroxyl group has a hydroxyl group at a partial end or side chain of the main chain, or both. That is, the siloxane compound having a hydroxyl group in the present invention may be a siloxane compound having a hydroxyl group at a partial end or side chain of the main chain, or may be a siloxane compound having a hydroxyl group at both a partial end and side chain of the main chain. The above siloxane compound having a hydroxyl group is a hydroxyl group-containing siloxane compound other than a siloxane compound having hydroxyl groups at both ends of the main chain. Here, the end of the main chain refers to the end of the longest part of the molecular chain in the molecular structure (the straight-chain part having the largest number of constituent atoms in the molecular structure).

[0091] Due to having a hydroxyl group, the siloxane compound having a specific structure easily reacts or interacts with the functional groups on the surface of the heat-conductive filler. And since the siloxane compound having a hydroxyl group does not have hydroxyl groups at both ends, the two ends do not react or interact with the heat-conductive filler. Therefore, it is considered that the dispersibility of the heat-conductive filler in the composition can be improved, and the viscosity can be effectively reduced.

[0092] The siloxane compound having a hydroxyl group of the present invention may have only 1 hydroxyl group, or may have 2 or more hydroxyl groups. It should be noted that there is no particular limitation on the upper limit of the number of hydroxyl groups, preferably 6 or less, more preferably 3 or less. Among them, in particular, a siloxane compound having 2 hydroxyl groups is preferred because of its high viscosity reduction effect.

[0093] The number of hydroxyl groups in the siloxane compound having a hydroxyl group in the present invention may be 1. As an embodiment, a siloxane compound having a hydroxyl group only at one end of the main chain can be cited.

[0094] The siloxane compound having a hydroxyl group in the present invention has a siloxane backbone (-Si-O-), and the number of repeating units n of the siloxane backbone is preferably 11 or more. The number of repeating units n of the siloxane backbone is preferably 11 or more and 350 or less, more preferably 20 or more and 300 or less, further preferably 50 or more and 270 or less, and further preferably 100 or more and 250 or less. When the number of repeating units n of the above siloxane backbone is above the above lower limit, the compatibility with the organopolysiloxane forming the matrix is improved, and further, an increase in volatile components can be suppressed. In addition, when the number of repeating units n of the above siloxane backbone is below the above upper limit, it is easy to adjust the viscosity of the composition to a lower level.

[0095] The polymer dispersant in the present invention is contained in the polymer composition. When the total amount of the polymer composition is specified as 100% by mass, considering the effective reduction of the viscosity of the composition, the content of the polymer dispersant in the polymer composition is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 30% by mass or less, and further preferably 3% by mass or more and 15% by mass or less.

[0096] It should be noted that the total amount of the polymer composition mentioned here refers to the total amount of the components forming the polymer matrix. The polymer composition contains not only organic polymers such as organopolysiloxane, but also additives such as plasticizers and dispersants, but does not include components volatilized during the manufacturing process and thermal conductive fillers. Therefore, it can also be said that the total amount of the polymer composition is the amount obtained by subtracting the compounding amounts of the thermal conductive filler and the volatile substance from the total amount of the mixed composition used to form the thermal conductive layer.

[0097] When the content of the polymer matrix is expressed as a filling rate (volume filling rate) based on volume, it is preferably 15% by volume or more and 50% by volume or less, more preferably 17% by volume or more and 46% by volume or less, and further preferably 20% by volume or more and 42% by volume or less, relative to the total amount of the thermal conductive sheet.

[0098] (Thermal Conductive Filler)

[0099] The thermal conductive filler contained in the thermal conductive layer is preferably dispersed in the polymer matrix and retained in the polymer matrix. As the thermal conductive filler, anisotropic fillers and non-anisotropic fillers can be cited, and it is preferable to use at least anisotropic fillers.

[0100] The anisotropic filler is preferably oriented in the thickness direction of the heat-conducting sheet. Thus, the heat-conducting layer can easily improve its heat conductivity. It should be noted that when the anisotropic filler is oriented in the thickness direction, the long-axis direction does not need to be strictly parallel to the thickness direction. Even if the long-axis direction is slightly inclined with respect to the thickness direction, it is regarded as being oriented in the thickness direction. Specifically, an anisotropic filler with a long-axis direction inclination of less than about 20° is also regarded as an anisotropic filler oriented in the thickness direction. If such anisotropic fillers are in the majority in the heat-conducting sheet (for example, more than 60% of the total number of all anisotropic fillers, preferably more than 80%), it is regarded as being oriented in the thickness direction.

[0101] Relative to 100 parts by mass of the polymer matrix, the content of the heat-conducting filler is preferably 150 parts by mass or more and 3000 parts by mass or less, more preferably 200 parts by mass or more and 1800 parts by mass or less, and still more preferably 300 parts by mass or more and 1000 parts by mass or less. By setting the content of the heat-conducting filler to 150 parts by mass or more, a certain heat conductivity can be imparted to the heat-conducting layer. And by setting it to 3000 parts by mass or less, the heat-conducting filler can be properly dispersed in the polymer matrix. In addition, it is also possible to prevent the viscosity of the mixed composition described later from becoming too high beyond necessity.

[0102] In addition, the volume filling rate of the heat-conducting filler relative to the total amount of the heat-conducting layer is preferably 40% by volume or more and 85% by volume or less, more preferably 48% by volume or more and 83% by volume or less, and still more preferably 56% by volume or more and 80% by volume or less. By setting the volume filling rate of the heat-conducting filler to the above lower limit or more, a certain heat conductivity can be imparted to the heat-conducting layer. In addition, by setting the volume filling rate of the heat-conducting filler to the upper limit or less, the manufacture of the heat-conducting layer becomes easy.

[0103] [Anisotropic filler]

[0104] The anisotropic filler is a filler with an anisotropic shape and is a filler capable of orientation. Examples of the anisotropic filler include fibrous materials and flaky materials. The anisotropic filler has a high aspect ratio. Specifically, the aspect ratio exceeds 2, and the aspect ratio is preferably 5 or more. By making the aspect ratio greater than 2, it is easy to orient the anisotropic filler in one direction such as the thickness direction, and it is easy to improve the heat conductivity in one direction such as the thickness direction of the heat-conducting layer. In addition, there is no particular limitation on the upper limit of the aspect ratio, and it is 100 in practical use.

[0105] It should be noted that the aspect ratio refers to the ratio of the length in the long-axis direction of the anisotropic filler to the length in the short-axis direction. For fibrous materials, it refers to the fiber length / fiber diameter, and for flaky materials, it refers to the length in the long-axis direction of the flaky material / thickness.

[0106] With respect to 100 parts by mass of the polymer matrix, the content of the anisotropic filler in the heat conductive layer is preferably 10 parts by mass or more and 500 parts by mass or less, more preferably 30 parts by mass or more and 300 parts by mass or less, and still more preferably 50 parts by mass or more and 250 parts by mass or less.

[0107] By setting the content of the anisotropic filler to 10 parts by mass or more, it is easy to improve the thermal conductivity. In addition, by setting it to 500 parts by mass or less, the viscosity of the mixed composition described later is likely to become appropriate, and the orientation of the anisotropic filler becomes good. Moreover, the dispersibility of the anisotropic filler in the polymer matrix also becomes good.

[0108] When the anisotropic filler is a fiber material, its average fiber length is preferably 10 μm or more and 300 μm or less, more preferably 20 μm or more and 200 μm or less, and still more preferably 30 μm or more and 100 μm or less. When the average fiber length is 10 μm or more, the anisotropic fillers appropriately contact each other inside the heat conductive layer, ensuring the heat transfer path, and the thermal conductivity of the heat conductive layer becomes good.

[0109] On the other hand, if the average fiber length is set to 500 μm or less, the volume of the anisotropic filler becomes small, and high filling can be performed in the binder component.

[0110] In addition, the average fiber length of the fiber material is preferably shorter than the thickness of the heat conductive sheet. By making it shorter than the thickness, it is possible to prevent the fiber material from protruding from the surface of the heat conductive sheet more than necessary.

[0111] It should be noted that the above average fiber length can be calculated by observing the anisotropic filler with a microscope. More specifically, for example, an electron microscope or an optical microscope can be used to measure the fiber lengths of any 50 anisotropic fillers, and their average value (arithmetic mean) is used as the average fiber length.

[0112] In addition, when the anisotropic filler is a flaky material, its average particle size is preferably 5 μm or more and 1000 μm or less, more preferably 8 μm or more and 750 μm or less, and still more preferably 10 μm or more and 500 μm or less. Among them, when the orientation method described later is the magnetic field orientation method, it is preferably 5 μm or more and 300 μm or less, more preferably 8 μm or more and 200 μm or less, and still more preferably 10 μm or more and 100 μm or less. By making the average particle size 5 μm or more, it is easy for the anisotropic fillers in the heat conductive layer to contact each other, ensuring the heat transfer path, and the thermal conductivity of the heat conductive layer becomes good. On the other hand, if the average particle size is made 300 μm or less, the volume of the heat conductive sheet becomes low, and the anisotropic filler can be highly filled in the binder component.

[0113] In addition, in the case where the orientation method is the flow orientation method, the average particle diameter of the flaky material is preferably 5 μm or more and 1000 μm or less, more preferably 10 μm or more and 750 μm or less, and still more preferably 15 μm or more and 500 μm or less. By making the average particle diameter 5 μm or more, it is easy for the anisotropic fillers in the heat conductive layer to come into contact with each other, ensuring the heat transfer path and making the heat conductivity of the heat conductive layer good. On the other hand, if the average particle diameter is 1000 μm or less, the volume of the heat conductive sheet becomes low, and the anisotropic fillers can be highly filled in the binder component.

[0114] It should be noted that the average particle diameter of the flaky filler is D50, which can be calculated by observing the flaky filler with a microscope and taking the major axis as the diameter. More specifically, it refers to, for example, measuring the major axis of any 500 or more flaky fillers using an electron microscope or an optical microscope, and it is the particle diameter corresponding to the cumulative frequency of 50%. Specifically, the flaky filler can be used as a sample, and it can be obtained from the particle size distribution curve with the horizontal axis specified as the particle size and the vertical axis specified as the cumulative frequency. This particle size distribution curve is a quantity-based particle size distribution curve obtained by successively accumulating the flaky fillers with small particle sizes.

[0115] For the anisotropic filler, a known material having heat conductivity can be used. In the case of orientation by magnetic field orientation as described later, it is sufficient to have diamagnetism. On the other hand, in the case of orientation by flow orientation or without orienting the anisotropic filler, it is not necessary to have diamagnetism.

[0116] Specific examples of the anisotropic filler include carbon materials represented by carbon fibers or flaky carbon powder, metal materials or metal oxides represented by metal fibers, boron nitride or metal nitrides, metal carbides, metal hydroxides, poly(phenylene benzoxazole) fibers, etc. Among them, carbon materials are preferred because of their low specific gravity and good dispersibility in the binder component, and among them, graphitized carbon materials with high thermal conductivity are more preferred. The graphitized carbon material has diamagnetism because the graphite planes are aligned in a specified direction.

[0117] In addition, boron nitride is also preferably used as the anisotropic filler. Boron nitride is not particularly limited, and it is preferably used in the form of flaky materials. The flaky boron nitride can be aggregated or not aggregated, and it is preferred that part or all of it is not aggregated. It should be noted that boron nitride and the like also have diamagnetism because the crystal planes are aligned in a specified direction.

[0118] In addition, the anisotropic filler is not particularly limited. The thermal conductivity along the anisotropic direction (i.e., the major axis direction) is usually 30 W / m·K or more, preferably 60 W / m·K or more, more preferably 100 W / m·K or more, and further preferably 200 W / m·K or more. There is no particular limitation on the upper limit of the thermal conductivity of the anisotropic filler, for example, it is 2000 W / m·K or less. The thermal conductivity can be measured by a laser flash method or the like.

[0119] One type of anisotropic filler can be used alone, or two or more types can be used in combination. For example, as the anisotropic filler, an anisotropic filler having at least two different average particle diameters or average fiber lengths can be used. It is considered that if anisotropic fillers of different sizes are used, the smaller anisotropic fillers enter between the relatively larger anisotropic fillers, whereby the anisotropic fillers can be densely packed in the binder component, and the heat conduction efficiency can be improved.

[0120] In addition, the anisotropic filler preferably contains the above-mentioned fiber material. As described later, in the heat-conducting layer containing the fiber material, the fiber material falls off due to slicing, and irregularities are formed on the surface, and the adhesiveness is likely to decrease. However, in the present invention, for example, when an adhesive is infiltrated into the heat-conducting layer or an adhesive layer is provided on at least one surface of the heat-conducting layer, the adhesive or the adhesive layer enters the recesses, so that even in the case of a heat-conducting layer having a fiber material, the adhesiveness can be sufficiently improved.

[0121] In addition, from the viewpoint of good thermal conductivity, it is preferable that the heat-conducting layer contains a flaky material as an anisotropic filler in addition to the fiber material. In this case, the content ratio of the flaky material to the fiber material (flaky material / fiber material) is, for example, 0.01 or more and 1 or less, preferably 0.02 or more and 0.5 or less, and more preferably 0.1 or more and 0.3 or less on a mass basis.

[0122] The carbon fiber used as the anisotropic filler is preferably graphitized carbon fiber. In addition, as the flaky carbon powder, flaky graphite powder is preferably used. As the anisotropic filler, it is preferable to use graphitized carbon fiber and flaky graphite powder in combination.

[0123] The crystal planes of graphite in the graphitized carbon fiber are connected in the fiber axis direction, and high thermal conductivity is provided in the fiber axis direction. Therefore, by making the fiber axis direction coincide with a specified direction, the thermal conductivity in a specific direction can be improved. And in the flaky graphite powder, the crystal planes of graphite are connected in the in-plane direction of the flaky surface, and high thermal conductivity is provided in the in-plane direction. Therefore, by making the flaky surface coincide with a specified direction, the thermal conductivity in a specific direction can be improved. The graphitized carbon fiber and the flaky graphite powder preferably have a high degree of graphitization.

[0124] As the graphitized carbon materials such as the above-mentioned graphitized carbon fiber and flaky graphite powder, materials formed by graphitizing the following raw materials can be used. For example, condensed polycyclic hydrocarbon compounds such as naphthalene, PAN (polyacrylonitrile), condensed heterocyclic compounds such as pitch, etc. are exemplified, and graphitized mesophase pitch, polyimide, and polybenzoxazole with a high degree of graphitization are particularly preferably used. For example, by using mesophase pitch, in the spinning process described later, the pitch is oriented along the fiber axis direction due to its anisotropy, and graphitized carbon fiber with excellent thermal conductivity in the fiber axis direction can be obtained.

[0125] Regarding the usage mode of mesophase pitch in graphitized carbon fiber, there is no particular limitation as long as it can be spun. Mesophase pitch can be used alone or in combination with other raw materials. However, considering high thermal conductivity, spinnability, and quality stability, it is most preferable to use mesophase pitch alone, that is, graphitized carbon fiber with a mesophase pitch content of 100%.

[0126] For graphitized carbon fiber, materials obtained by successively performing various treatments of spinning, infusibilization, and carbonization, pulverizing or cutting into a specified particle size and then graphitizing, or carbonizing and then pulverizing or cutting and then graphitizing can be used. When pulverizing or cutting is performed before graphitization, on the newly exposed surface due to pulverization, polycondensation reaction and cyclization reaction are likely to occur during the graphitization treatment, so the degree of graphitization can be increased, and graphitized carbon fiber with further improved thermal conductivity can be obtained. On the other hand, when the carbon fiber after spinning is graphitized and then pulverized, the graphitized carbon fiber is rigid, so it is easy to pulverize, and carbon fiber powder with a narrow fiber length distribution can be obtained by pulverizing for a short time.

[0127] As described above, the average fiber length of graphitized carbon fiber is preferably 10 μm or more and 300 μm or less, more preferably 20 μm or more and 200 μm or less, and further preferably 30 μm or more and 100 μm or less. In addition, as described above, the aspect ratio of graphitized carbon fiber exceeds 2, and is preferably 5 or more. The thermal conductivity of graphitized carbon fiber is not particularly limited, and the thermal conductivity in the fiber axis direction is preferably 400 W / m·K or more, and more preferably 800 W / m·K or more.

[0128] When the heat-conducting layer contains anisotropic fillers, they may or may not be exposed on the surface of the heat-conducting layer, and exposure is preferred. By exposing the anisotropic fillers, the anisotropic fillers come into contact with adherends such as heat-generating bodies and heat-dissipating bodies, thus easily reducing the thermal resistance value. In addition, if the anisotropic fillers are exposed, it is difficult to improve the adhesion to the adherend, but even in such a case, in the present invention, by providing an adhesive or an adhesive layer, it is easy to improve the adhesion.

[0129] [Non-anisotropic filler]

[0130] The heat-conducting filler in the present invention may contain non-anisotropic fillers, and it is preferred to use the above-mentioned anisotropic filler and non-anisotropic filler in combination.

[0131] For non-anisotropic fillers, especially by using them in combination with anisotropic fillers oriented in one direction such as the thickness direction, and inserting them into the gaps between the oriented anisotropic fillers, the thermal conductivity can be further improved. Non-anisotropic fillers are fillers whose shape is substantially non-anisotropic, and they are fillers that do not orient along the specified direction even in an environment where anisotropic fillers orient along the specified direction under the generation of magnetic field lines or the action of shear force described below.

[0132] The aspect ratio of the non-anisotropic filler is 2 or less, preferably 1.5 or less. Such non-anisotropic fillers with a low aspect ratio are easily arranged in the gaps between anisotropic fillers when used in combination with anisotropic fillers, and it is easy to improve the thermal conductivity. In addition, by making the aspect ratio 2 or less, an increase in the viscosity of the mixed composition described below can be prevented, and high filling can be achieved.

[0133] Specific examples of non-anisotropic fillers include, for example, metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides other than metals, etc. In addition, for the shape of non-anisotropic fillers, spherical, polyhedral, irregular-shaped powders, etc. can be cited.

[0134] Among non-anisotropic fillers, as metals, aluminum, copper, nickel, etc. can be exemplified. As metal oxides, alumina represented by alumina, magnesia, zinc oxide, etc. can be exemplified. As metal nitrides, aluminum nitride, etc. can be exemplified. As metal hydroxides, aluminum hydroxide can be cited. Furthermore, as carbon materials, spherical graphite, etc. can be cited. As oxides, nitrides, carbides other than metals, quartz, boron nitride, silicon carbide, etc. can be cited.

[0135] Among them, considering the high thermal conductivity and the easy availability of spherical materials, alumina and aluminum are preferred.

[0136] The non-anisotropic filler may use one of the above-mentioned non-anisotropic fillers alone, or two or more of them may be used in combination.

[0137] The average particle diameter of the non-anisotropic filler is, for example, 0.1 μm or more and 200 μm or less, preferably 0.5 μm or more and 100 μm or less, and more preferably 1 μm or more and 70 μm or less.

[0138] In addition, when using non - anisotropic fillers in combination with anisotropic fillers, the average particle diameter of the non - anisotropic fillers is preferably 0.1 μm or more and 50 μm or less, more preferably 0.5 μm or more and 35 μm or less, and still more preferably 1 μm or more and 15 μm or less. By making the average particle diameter 50 μm or less, even when used in combination with anisotropic fillers, adverse conditions such as disturbing the orientation of anisotropic fillers are less likely to occur. In addition, by making the average particle diameter 0.1 μm or more, the specific surface area of the non - anisotropic fillers does not become larger than necessary, and even when a large amount is compounded, the viscosity of the mixed composition is not likely to increase, and it is easy to highly fill the non - anisotropic fillers.

[0139] As the non - anisotropic fillers, for example, non - anisotropic fillers having at least two mutually different average particle diameters can be used.

[0140] It should be noted that the average particle diameter of the non - anisotropic fillers can be measured by observing with an electron microscope or the like. More specifically, for example, an electron microscope or an optical microscope can be used to measure the particle diameters of any 500 or more non - anisotropic fillers, and D50 can be obtained by the same method as for the flaky fillers.

[0141] Relative to 100 parts by mass of the polymer matrix, the content of the non - anisotropic fillers is preferably 50 parts by mass or more and 2500 parts by mass or less, more preferably 100 parts by mass or more and 1500 parts by mass or less, and still more preferably 200 parts by mass or more and 750 parts by mass or less. By setting it to 50 parts by mass or more, the thermal conductivity of the heat - conducting sheet can be made good. On the other hand, by setting it to 1500 parts by mass or less, the non - anisotropic fillers are appropriately dispersed in the binder component, and the effect of improving the thermal conductivity corresponding to the content can be obtained. In addition, an excessive increase in the viscosity of the mixed composition can also be prevented.

[0142] The mass ratio of the content of the non - anisotropic fillers to the content of the anisotropic fillers is not particularly limited, preferably 0.5 or more and 15 or less, more preferably 1 or more and 10 or less, and preferably 1.1 or more and 7 or less. By making the mass ratio within the above range, the non - anisotropic fillers are moderately filled between the anisotropic fillers, and an effective heat - conducting path can be formed, so that the thermal conductivity of the heat - conducting sheet can be further improved.

[0143] In the heat-conducting layer, within the range that does not impair the function of the heat-conducting layer, components other than the above can be incorporated into the polymer matrix. Specifically, for example, at least one selected from a dispersant, a flame retardant, an antioxidant, a colorant, an anti-settling agent, etc. can be cited. In addition, in the case of crosslinking and curing the curable polymer composition as described above, as additives, a crosslinking promoter, a curing promoter, a curing catalyst, etc. that promote crosslinking and curing can be incorporated. When the polymer matrix is an organopolysiloxane, a platinum catalyst can be used as the curing catalyst.

[0144] The surface of the heat-conducting layer is preferably a cut surface. By making the surface of the heat-conducting layer a cut surface, as described above, anisotropic fillers, etc. are easily exposed on the surface of the heat-conducting layer, and the thermal resistance value can be effectively reduced. The heat-conducting sheet can have a cut surface on one surface or two surfaces, and preferably the adhesive surface, the surface where the adhesive layer is provided is the cut surface. It should be noted that, as will be described later, the cut surface refers to a surface formed by cutting with a shear knife, a laser, etc.

[0145] The cut surface is mostly in a state with large unevenness due to the protrusion and shedding of anisotropic fillers, but by filling the concave portions with the adhesive layer, the air layer can be reduced during use, and the thermal resistance value can be improved while the adhesion is enhanced.

[0146] In addition, for the heat-conducting sheet, it is also preferable that the surface is a ground surface. By making at least one surface of the heat-conducting sheet a ground surface, the thermal resistance value can be reduced more effectively. The heat-conducting sheet can have a ground surface on one surface or two surfaces, and preferably the adhesive surface, the surface where the adhesive layer is provided is the ground surface, and particularly preferably this surface is both a cut surface and a ground surface at the same time. Since the smoothness of the ground surface is relatively high, combined with the case of providing the adhesive layer, it is easy to improve the adhesion to the adherend.

[0147] The thickness of the heat-conducting layer is not particularly limited. For example, it is about 1200 μm or less. Considering from the aspect of being applicable to semiconductor applications and preventing the thermal resistance value from becoming large, it is better to be thinner, preferably 500 μm or less, more preferably 300 μm or less, and further preferably 200 μm or less. In addition, considering from the aspect of easily achieving good adhesion to the adherend, the thickness of the heat-conducting layer is preferably 50 μm or more, more preferably 80 μm or more, and further preferably 120 μm or more. It should be noted that the thickness of the heat-conducting layer refers to the initial thickness measured in the state where no load acts in the thickness direction.

[0148] When used in the configuration between a semiconductor chip and a heat sink, the thickness of the heat-conducting layer is preferably 200 μm or less, more preferably 150 μm or less, further preferably 130 μm or less, preferably 50 μm or more, more preferably 80 μm or more, and further preferably 100 μm or more.

[0149] When used between a test head and a semiconductor package in a semiconductor inspection process, considering good heat dissipation, the thickness of the heat-conducting layer is preferably 2000 μm or less, more preferably 1500 μm or less, and still more preferably 1000 μm or less. Regarding the lower limit value of the thickness of the heat-conducting layer, as a range applicable to semiconductor inspection applications, it is preferably 150 μm or more, but there is no particular limitation, and it can be 200 μm or more, or 300 μm or more.

[0150] (Adhesive layer)

[0151] For the heat-conducting sheet of the present invention, it is preferable to provide an adhesive layer on at least one surface of the heat-conducting layer. At this time, the heat-conducting sheet can make at least one surface of the heat-conducting layer adhesive through the adhesive layer. And the heat-conducting layer having an adhesive surface through the adhesive layer can be used as the heat-conducting sheet or disposed on the surface of the heat-conducting sheet, thereby making the surface of the heat-conducting sheet adhesive as described above.

[0152] The adhesive layer can be provided only on any one surface of the heat-conducting layer, or on both surfaces of the heat-conducting layer. Thus, a structure in which both surfaces of the heat-conducting sheet are adhesive can be formed. As the adhesive layer, an acrylic adhesive layer, a rubber adhesive layer, a urethane adhesive layer, a silicone adhesive layer, etc. can be used. Among them, an acrylic adhesive layer is preferred. By using an acrylic adhesive layer, the adhesion to adherends such as a thermal spray machine, a radiator, and a semiconductor chip is likely to become high before and after high-temperature heating in a reflow soldering process or the like.

[0153] The acrylic adhesive layer is formed of an acrylic adhesive. The acrylic adhesive can contain an acrylic polymer as the main agent of the adhesive. The acrylic adhesive layer can exhibit adhesiveness by containing an acrylic polymer.

[0154] The acrylic adhesive layer may or may not have reactive double bonds, and preferably has reactive double bonds. When the acrylic adhesive layer has reactive double bonds, the reactive double bonds react by high-temperature heating or the like, so that the adhesiveness can disappear and the adhesion to the adherend can be improved. Therefore, in a state where the heat-conducting sheet is adhered to an adherend such as a thermal spray machine or a semiconductor chip, even when heated to a high temperature in a reflow soldering process or the like, the adhered state can be maintained, and peeling from the adherend can be prevented. In addition, in actual use, even when used in an environment at a relatively high temperature of about 150 °C, high adhesion can be maintained.

[0155] It should be noted that the reactive double bond is an unsaturated carbon-carbon double bond that does not form an aromatic ring. Representatively, it is composed of groups with structures represented by H2C=CH-* or H2C=CCH3-*(where * represents the bonding position). Specifically, vinyl, acryloyl, methacryloyl, etc. can be cited.

[0156] In addition to the reactive double bond, the acrylic polymer having a reactive double bond (acrylic polymer containing a reactive double bond) may also have functional groups such as hydroxyl, carboxyl, epoxy, amino, etc. in the side chain. Preferably, it has at least one of hydroxyl and carboxyl in the side chain, and more preferably has both hydroxyl and carboxyl.

[0157] For the acrylic polymer containing a reactive double bond, for example, an acrylic polymer having functional groups such as hydroxyl, carboxyl, epoxy, amino, etc. in the side chain [hereinafter, also referred to as acrylic polymer (X)] can be reacted with a reactive double bond-containing compound having a reactive group reactive with the functional group and a reactive double bond [hereinafter, also referred to as reactive double bond-containing compound (Y)] to obtain it.

[0158] As the acrylic polymer (X), as long as it contains a structural unit derived from (meth)acrylate, typically, it contains a structural unit derived from an alkyl (meth)acrylate as the main component. More specifically, as the acrylic polymer (X), copolymers of alkyl (meth)acrylate and functional group-containing monomers, copolymers of alkyl (meth)acrylate, functional group-containing monomers and other monomers other than them, etc. can be cited.

[0159] It should be noted that (meth)acrylate is used as a term representing either acrylate or methacrylate or both, and the same applies to other similar terms.

[0160] (Meth)acrylic acid alkyl ester is an ester of (meth)acrylic acid and an alkyl alcohol. The alkyl in the (meth)acrylic acid alkyl ester can be linear, can have a branched chain structure, or can have a cyclic structure.

[0161] As the (meth)acrylic acid alkyl ester, (meth)acrylic acid methyl ester, (meth)acrylic acid ethyl ester, (meth)acrylic acid propyl ester, (meth)acrylic acid n-butyl ester, (meth)acrylic acid isobutyl ester, (meth)acrylic acid tert-butyl ester, (meth)acrylic acid 2-ethylhexyl ester, (meth)acrylic acid n-octyl ester, (meth)acrylic acid isooctyl ester, (meth)acrylic acid isononyl ester, (meth)acrylic acid isomyristyl ester, (meth)acrylic acid stearyl ester, (meth)acrylic acid cyclohexyl ester, (meth)acrylic acid isobornyl ester, etc. can be cited.

[0162] (Meth)acrylic acid alkyl esters can be used alone or in combination of two or more.

[0163] For the (meth)acrylic acid alkyl ester, it is preferably a (meth)acrylic acid alkyl ester with 1 to 12 carbon atoms in the alkyl group, more preferably an acrylic acid alkyl ester with 2 to 8 carbon atoms in the alkyl group. The structural unit derived from the acrylic acid alkyl ester with 2 to 8 carbon atoms in the alkyl group can be the main component in the acrylic polymer (X). In the acrylic polymer (X), for example, it can be 50% by mass or more, preferably 60% by mass or more and 95% by mass or less, more preferably 70% by mass or more and 90% by mass or less.

[0164] Regarding the functional groups in the functional group-containing monomer, as described above, carboxyl group, hydroxyl group, amino group, and epoxy group can be cited, among which carboxyl group and hydroxyl group are preferred. As the monomer containing a carboxyl group, (meth)acrylic acid, crotonic acid, etc. can be cited, and among them, (meth)acrylic acid is more preferred.

[0165] In addition, as the monomer containing a hydroxyl group, for example, (meth)acrylic acid 2-hydroxyethyl ester, (meth)acrylic acid 2-hydroxypropyl ester, (meth)acrylic acid 3-hydroxypropyl ester, (meth)acrylic acid 2-hydroxybutyl ester, (meth)acrylic acid 4-hydroxybutyl ester, (meth)acrylic acid 5-hydroxypentyl ester, (meth)acrylic acid 6-hydroxyhexyl ester and other (meth)acrylic acid esters having a hydroxyl group, allyl alcohol, etc. can be cited. Among them, (meth)acrylic acid 2-hydroxyethyl ester and other (meth)acrylic acid esters having a hydroxyl group are preferred.

[0166] The structural unit derived from the functional group-containing monomer in the acrylic polymer (X) is, for example, about 1% by mass or more and 35% by mass or less, preferably 5% by mass or more and 30% by mass or less, more preferably 10% by mass or more and 25% by mass or less.

[0167] The functional group-containing monomer can be used alone or in combination of two or more.

[0168] As other monomers, monomers other than the (meth)acrylic acid alkyl ester and the above-mentioned functional group-containing monomer can be cited. As long as they can copolymerize with the (meth)acrylic acid alkyl ester and the functional group-containing monomer, there is no particular limitation. Specifically, styrene derivatives such as styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, divinylbenzene, compounds having a vinyl ester group such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, N-vinylmorpholine, (meth)acrylonitrile, N-cyclohexylmaleimide, N-phenylmaleimide, N-laurylmaleimide, N-benzylmaleimide, n-propyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, etc. can be cited. Other monomers can be used alone or in combination of two or more.

[0169] The compound (Y) containing a reactive double bond is a compound having a reactive group reactive with the above functional group and a reactive double bond. Examples of the reactive group include an isocyanate group, an epoxy group, a carboxyl group, a hydroxyl group, etc. Among these, an isocyanate group and an epoxy group are preferred, and an isocyanate group is more preferred.

[0170] It should be noted that the content of the reactive double bond contained in the acrylic adhesive layer can be adjusted by the amount of the functional group contained in the acrylic polymer (X) and the ratio of the above functional group reacting with the compound (Y) containing a reactive double bond. In addition, the amount of the functional group contained in the above acrylic polymer (X) can be adjusted by the ratio of the functional group-containing monomer used in synthesizing the acrylic polymer (X).

[0171] The acrylic polymer contained in the acrylic adhesive layer may be composed of an acrylic polymer containing a reactive double bond. In addition to the acrylic polymer containing a reactive double bond, an acrylic polymer not having a reactive double bond may also be contained. Further, the acrylic polymer may be composed of an acrylic polymer not having a reactive double bond. Examples of the acrylic polymer not having a reactive double bond include the above acrylic polymer (X).

[0172] For the acrylic adhesive, in addition to the above acrylic polymer, components usually blended in the adhesive may be contained, and additives such as a crosslinking agent, a tackifier, a filler, an antioxidant, an ultraviolet ray blocker, a plasticizer, a viscosity regulator, etc. may be appropriately contained.

[0173] The weight average molecular weight of the acrylic polymer is not particularly limited. For example, it is about 100,000 or more and 1,200,000 or less, preferably about 200,000 or more and 1,000,000 or less. It should be noted that the weight average molecular weight is measured using a gel permeation chromatograph (GPC) and is obtained as a polystyrene conversion value.

[0174] The adhesive layer may be provided on one surface of the heat conductive layer or on both surfaces of the heat conductive layer. It should be noted that the one surface or both surfaces mentioned here refer to the surfaces along the direction perpendicular to the thickness direction of the heat conductive layer, which are also the surfaces called the so-called main surfaces.

[0175] By providing the adhesive layer on both surfaces of the heat conductive layer, the adhesion of both surfaces of the heat conductive sheet to the adherend can be improved. Therefore, when the heat conductive sheet is used for semiconductor applications, for example, it can be adhered to both the semiconductor chip and the thermal sprayer with a high adhesive force. In addition, even when heated at a high temperature through a reflow soldering process or the like in a state of being adhered to them, it is easy to prevent the heat conductive sheet from peeling off from either the semiconductor chip or the thermal sprayer.

[0176] The weight per unit area of the adhesive layer on each surface is, for example, 0.05 mg / cm2 Above, preferably 0.1 mg / cm 2 Above, more preferably 0.15 mg / cm 2 Above, further preferably 0.3 mg / cm 2 Above, additionally, for example, 1.5 mg / cm 2 Below, preferably 1.3 mg / cm 2 Below, more preferably 1.1 mg / cm 2 Below, further preferably 0.9 mg / cm 2 Below. For the adhesive layer, by setting the basis weight per unit area to a certain amount or more, sufficient adhesiveness to the adherend can be ensured. Additionally, it is easy to make the amount of volatile components at 150°C reach a certain amount or more.

[0177] On the other hand, by setting the basis weight per unit area to a certain amount or less, it is easy to suppress the amount of volatile components at 150°C to a certain amount or less. Additionally, it is possible to prevent the thermal resistance value from decreasing due to the adhesive layer and easily ensure good thermal conductivity.

[0178] Preferably, the adhesive layer penetrates into the heat-conducting layer. Typically, a part of the adhesive layer may penetrate into the heat-conducting layer, but as long as the adhesiveness to the adherend can be exhibited through the adhesive layer, it may also penetrate entirely into the heat-conducting layer. By penetrating into the heat-conducting layer, the amount of the adhesive existing on the surface of the heat-conducting layer can be reduced, and the decrease in thermal conductivity caused by the adhesive layer can be suppressed.

[0179] Additionally, even if the adhesive penetrates into the heat-conducting layer, the heat-conducting sheet can ensure high sealing performance. The principle is not yet clear, but it is presumed that when the heat-conducting sheet is usually compressed etc. during use and pressurized, the adhesive that penetrates through this pressurization oozes out to the surface and improves the sealing performance.

[0180] It should be noted that for the adhesive layer, as described later, by immersing it in the bubbles formed by the volatilization of the volatile substance, an appropriate amount of the adhesive layer can penetrate into the heat-conducting layer.

[0181] Additionally, the adhesive layer can be formed so as to cover the entire surfaces of the heat-conducting layer, but as long as it can exhibit the adhesiveness to the adherend, it can also be formed in a partially covering manner.

[0182] It should be noted that the above shows the method of providing an adhesive layer on at least one surface of the heat-conducting layer, but it is not necessarily required to provide an adhesive layer. For example, the adhesive layer may not be provided, and at least one surface of the heat-conducting layer may have adhesiveness by including an adhesive in the heat-conducting layer. In this case, for example, by incorporating an adhesive into the mixed composition described later, the heat-conducting layer can be made to contain the adhesive. Examples of the adhesive contained in the heat-conducting layer include acrylic adhesives, rubber adhesives, urethane adhesives, and silicone adhesives, among which acrylic adhesives are preferred. The details of the acrylic adhesive are as described above. The above-mentioned adhesive may be a material that already has adhesiveness in the process of incorporating it into the mixed composition, or a material that does not have adhesiveness in the process of incorporating it into the mixed composition but exhibits adhesiveness according to external stimuli such as heat, pressure, and light.

[0183] When the heat-conducting layer contains an adhesive, the content of the adhesive in the heat-conducting layer may be, for example, 0.1 parts by mass or more and 20 parts by mass or less, preferably 0.3 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 12 parts by mass or less, based on 100 parts by mass of the polymer matrix.

[0184] (SAT coverage rate)

[0185] The SAT coverage rate (hereinafter, also referred to as "SAT coverage rate based on thermocompression bonding") of the heat-conducting sheet of the present invention during thermocompression bonding under the conditions of 150 °C, 10 minutes, and 30 psi is preferably 60% or more, more preferably 70% or more, and further preferably 80% or more. If the SAT coverage rate based on thermocompression bonding is above the above lower limit value, the initial sealing property becomes good. There is no particular limitation on the upper limit of the SAT coverage rate based on heat press bonding, as long as it is 100%, and practically it is, for example, 95%, preferably 90%, and more preferably 85%.

[0186] It should be noted that the SAT coverage rate based on thermocompression bonding can be obtained as follows. First, the heat-conducting sheet is clamped between a silicon wafer and a copper plate and thermocompression bonded under the conditions of 150 °C, 10 minutes, and 30 psi to obtain a sample. Then, the obtained sample is subjected to ultrasonic flaw detection inspection (SAT) to obtain an image of the bonding interface between the copper plate and the heat-conducting sheet. Next, binarization is performed by a prescribed image processing, and based on this binarized image, the SAT coverage rate can be obtained. The detailed steps are as described in the examples. Regarding the SAT coverage rate after high-temperature heating described later, it can be obtained in the same manner except that after pressing, it is further heated at 260 °C for 3 minutes.

[0187] The heat-conducting sheet of the present invention is hot-pressed under the conditions of 150°C, 10 minutes, and 30 psi, and then the SAT coverage rate (hereinafter, also referred to as "SAT coverage rate after high-temperature heating") after high-temperature heating at 260°C for 3 minutes is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more. When the SAT coverage rate after high-temperature heating is above the above lower limit value, after high-temperature heating such as in the reflow soldering process, the gap between the heat-conducting sheet and the adherend becomes smaller, and the adhesion to the adherend becomes good. The upper limit value of the SAT coverage rate after high-temperature heating is not particularly limited as long as it is 100%, and in practice, for example, it is 95%, preferably 90%, and more preferably 85%.

[0188] (E hardness)

[0189] For the heat-conducting layer of the present invention, the E-type hardness (hereinafter, also referred to as "E hardness") specified in JIS K6253 is preferably 10 or more and 80 or less, more preferably 20 or more and 70 or less, and further preferably 30 or more and 65 or less. When the E hardness is above the above lower limit value, it is easy to improve the mechanical strength of the heat-conducting sheet. In addition, when the E hardness is below the above upper limit value, a certain softness can be imparted to the heat-conducting sheet, and it is also easy to improve the adhesion to the adherend.

[0190] When the heat-conducting sheet is used by being disposed between a semiconductor chip and a heat sink, the E hardness of the heat-conducting layer is preferably 30 or more and 50 or less, more preferably 35 or more and 45 or less. When the E hardness is above the above lower limit value, it is easy to improve the mechanical strength of the heat-conducting sheet. In addition, when the E hardness is below the above upper limit value, a certain softness can be imparted to the heat-conducting sheet, and it is also easy to improve the adhesion to the adherend.

[0191] When the heat-conducting sheet is used by being disposed between a test head and a semiconductor package in a semiconductor inspection process, the E hardness of the heat-conducting layer is preferably 30 or more and 80 or less, more preferably 40 or more and 70 or less. When the E hardness is above the above lower limit value, it is easy to improve the mechanical strength of the heat-conducting sheet, and even when used under high loads, deformation of the sheet can be suppressed. In addition, when the E hardness is below the above upper limit value, a certain softness can be imparted to the heat-conducting sheet, and it is also easy to improve the adhesion to the adherend.

[0192] [Manufacturing method of heat-conducting sheet]

[0193] The heat-conducting sheet of the present invention can be manufactured by a method having at least the following steps 1 to 3. However, the heat-conducting sheet of the present invention can also be manufactured by methods other than the following manufacturing method.

[0194] Step 1: A step of obtaining a mixed composition by at least mixing a curable polymer composition and a heat-conducting filler;

[0195] Step 2: A step of obtaining a cured product by curing the mixed composition through heating;

[0196] Step 3: A step of coating an adhesive on the surface of the cured product.

[0197] (Step 1)

[0198] In Step 1, the mixed composition can be obtained by at least mixing a curable polymer composition and a heat-conductive filler. Preferably, a volatile substance is further mixed in the mixed composition. In addition, other components such as additives that are appropriately blended as needed can also be added to the mixed composition.

[0199] In Step 1, as long as the above-mentioned components can be mixed to obtain the mixed composition, there are no particular limitations on the mixing method and the mixing order. The curable polymer composition, the heat-conductive filler, the volatile substance added as needed, and other components optionally added as needed can be appropriately mixed in any order to obtain the mixed composition.

[0200] For the curable polymer composition, as described above, for example, it can be composed of a main agent and a curing agent (for example, in an addition reaction type silicone, an alkenyl-containing organopolysiloxane and a hydrogen organopolysiloxane). In such a case, the main agent, the curing agent, the heat-conductive filler, the volatile substance optionally added as needed, and other components can be mixed in any order to obtain the mixed composition.

[0201] It should be noted that the form of the mixed composition can be either a single-component type or a two-component type formed by combining a first component and a second component. The two-component type is a substance that obtains the mixed composition by mixing the first component and the second component during use.

[0202] (Volatile Substance)

[0203] For the volatile substance used in the present invention, any component that volatilizes in Step 2 described below is acceptable. The volatile substance volatilizes by heating during curing, thereby increasing the content ratio of the heat-conductive filler in the heat-conductive sheet. In addition, the viscosity of the mixed composition decreases by containing the volatile substance. Therefore, it is easy to increase the blending amount of the heat-conductive filler, and it is easy to orient the anisotropic filler in a specified direction by magnetic orientation or the like described below.

[0204] Moreover, since a large number of fine bubbles are formed in the cured product due to the volatilization of the volatile substance, the adhesive easily penetrates into the interior of the heat-conductive layer in Step 3 described below.

[0205] In addition, the volatile substance may be a compatible substance that is compatible with or soluble in the curable polymer composition. When the volatile substance is a compatible substance, the curable polymer composition and the volatile substance can be uniformly mixed. Therefore, it is easy to reduce the viscosity or increase the compounding amount of the thermal conductive filler. Moreover, the bubbles formed due to the volatilization of the volatile substance can also be made fine and uniform.

[0206] The volatile substance is preferably a substance that is liquid at normal temperature (25 °C) and 1 atmospheric pressure.

[0207] Examples of the volatile substance include alkoxysilane compounds and hydrocarbon solvents. These compounds can improve the solubility or compatibility with the curable polymer composition. Therefore, it is easy to reduce the viscosity of the mixed composition or increase the compounding amount of the thermal conductive filler. In addition, it is easy to make the bubbles formed due to the volatilization of the volatile substance fine and uniform.

[0208] The volatile substance may be used alone or in combination of two or more.

[0209] As the volatile substance, an alkoxysilane compound is preferably used. By using an alkoxysilane compound, problems such as roughness are not seen on the surface of the thermal conductive sheet obtained by curing, and the appearance is good.

[0210] The alkoxysilane compound used as the volatile substance is a compound having a structure in which 1 to 3 of the 4 bonds carried by a silicon atom (Si) are bonded to alkoxy groups, and the remaining bonds are bonded to organic substituents. By having alkoxy groups and organic substituents, the alkoxysilane compound can improve the compatibility with the curable polymer composition, particularly the curable polymer composition composed of organopolysiloxane.

[0211] Examples of the alkoxy group possessed by the alkoxysilane compound include methoxy, ethoxy, propoxy, butoxy, pentyloxy, and hexyloxy. The alkoxysilane compound may be contained as a dimer in the curable polymer composition.

[0212] Among the alkoxysilane compounds, from the viewpoint of ease of acquisition, an alkoxysilane compound having at least one of methoxy and ethoxy is preferred. From the viewpoints of compatibility and solubility with the curable polymer composition, the number of alkoxy groups possessed by the alkoxysilane compound is preferably 2 or 3, more preferably 3. Specifically, the alkoxysilane compound is preferably at least one selected from trimethoxysilane compounds, triethoxysilane compounds, dimethoxysilane compounds, and diethoxysilane compounds.

[0213] Examples of the functional groups contained in the organic substituents of the alkoxysilane compound include an acryloyl group, an alkyl group, a carboxyl group, a vinyl group, a methacryloyl group, an aromatic group, an amino group, an isocyanate group, an isocyanurate group, an epoxy group, a hydroxyl group, and a mercapto group. Here, when a platinum catalyst is used as a curing catalyst for the curable polymer composition composed of an organopolysiloxane, it is preferable to select and use an alkoxysilane compound that does not easily affect the curing reaction of the organopolysiloxane. Specifically, when an addition reaction type organopolysiloxane using a platinum catalyst is used, the organic substituents of the alkoxysilane compound preferably do not contain an amino group, an isocyanate group, an isocyanurate group, a hydroxyl group, or a mercapto group.

[0214] From the aspect of compatibility with the curable polymer composition composed of an organopolysiloxane, the alkoxysilane compound preferably contains an alkylalkoxysilane compound having an alkyl group bonded to a silicon atom, that is, an alkoxysilane compound having an alkyl group as an organic substituent. Therefore, a dialkyldialkoxysilane compound or an alkyltrialkoxysilane compound is preferable, and an alkyltrialkoxysilane compound is more preferable.

[0215] The number of carbon atoms of the alkyl group bonded to the silicon atom can be, for example, 1 to 16. In addition, in a trialkoxysilane compound such as a trimethoxysilane compound or a triethoxysilane compound, the number of carbon atoms of the above alkyl group is preferably 6 or more, more preferably 8 or more, and preferably 12 or less, more preferably 10 or less.

[0216] On the other hand, in a dialkoxysilane compound such as a dimethoxysilane compound or a diethoxysilane compound, the number of carbon atoms of the above alkyl group may be 1 or more, and preferably 10 or less, more preferably 6 or less, and further preferably 4 or less.

[0217] Examples of the alkoxysilane compound containing an alkyl group include methyltrimethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, di-n-propyldimethoxysilane, di-n-propyldiethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, methylcyclohexyldimethoxysilane, methylcyclohexyldiethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, etc.

[0218] Among alkyl-containing alkoxysilane compounds, n-decyltrimethoxysilane and n-octyltriethoxysilane are more preferably considered from the aspect of compatibility with the organopolysiloxane constituting the curable polymer composition.

[0219] As the hydrocarbon solvent used as the volatile substance, aromatic hydrocarbon solvents can be cited. Among them, from the aspect of compatibility with the curable polymer composition, aromatic hydrocarbon solvents are preferred. As the aromatic hydrocarbon solvents, aromatic hydrocarbon solvents having about 6 to 10 carbon atoms can be cited, and examples thereof include toluene, xylene, mesitylene, ethylbenzene, propylbenzene, butylbenzene, tert-butylbenzene, etc., and toluene, xylene, etc. are preferred.

[0220] In the mixed composition, the content of the volatile substance is preferably 1 part by mass or more and 60 parts by mass or less with respect to 100 parts by mass of the curable polymer composition. If it is 1 part by mass or more, the effect of containing the volatile substance is easily exhibited. For example, an appropriate amount of fine bubbles can be formed in the polymer matrix. In addition, by setting it to 60 parts by mass or less, an effect commensurate with the amount of the volatile substance used can be obtained. Considering these aspects, the above content of the volatile substance is more preferably 1.5 parts by mass or more and 50 parts by mass or less, and further preferably 2 parts by mass or more and 35 parts by mass or less.

[0221] It should be noted that the volatile substance is preferably substantially completely volatilized by the heating in Step 2. It is preferred that the heat dissipation sheet does not contain the volatile substance, but as long as the amount of the volatile component is within the above-specified range, the heat dissipation sheet may also contain a small amount of the volatile substance.

[0222] It should be noted that the details of the components other than the volatile substance in the mixed composition (that is, the curable polymer composition, the heat conduction filler, other additives, etc.) are as described above. In addition, the content of the heat conduction filler in the mixed composition is also as described above. However, in the above content, the content of each component represents the amount based on 100 parts by mass of the polymer matrix, but in the mixed composition, it means the amount based on 100 parts by mass of the curable polymer composition.

[0223] (Step 2)

[0224] Step 2 is a step of curing the mixed composition by heating. The temperature for heating the mixed composition is not particularly limited as long as the curable polymer composition can be cured by heating, and it may be higher than room temperature (25°C), preferably heated at a temperature of 50°C or higher, more preferably 70°C or higher. In addition, the heating temperature is not particularly limited as long as it is a temperature at which the heat conductive layer and the mixed composition do not undergo thermal deterioration, for example, it is 200°C or lower, preferably 180°C or lower, more preferably 160°C or lower. In addition, the heating can be carried out in one stage or in two or more stages. In the case of carrying out in two or more stages, as long as the heating temperature is within the above range in at least one stage, it is preferred that the heating temperature is within the above range in all stages. In addition, it is preferred that at least in the heating of the first stage, the heating is carried out at a temperature lower than the boiling point of the volatile substance. In addition, the total heating time is, for example, about 10 minutes or more and 24 hours or less. In the case of carrying out in two or more stages, for example, the mixed composition can be semi-cured in the first stage (primary curing), and the mixed composition can be completely cured by heating in the subsequent second stage and later (secondary curing). In addition, the curing can also be completely cured by primary curing, and the heating after the second stage is not accompanied by curing.

[0225] As described later, when the molded body obtained from the mixed composition is sliced into a sheet-shaped molded body, it is also preferred to carry out primary curing by heating in the first stage before slicing, and further heating in the second stage and later (secondary curing) after slicing. By heating after slicing, it is easy to volatilize the volatile substance by heating in the second stage and later.

[0226] In the case of curing in two or more stages, the heating in the first stage (primary curing) can be carried out, for example, at 50°C or higher and 120°C or lower, preferably 60°C or higher and 100°C or lower, more preferably 70°C or higher and 90°C or lower. In addition, the heating in the second stage and later (secondary curing) can be carried out at a temperature higher than that of the primary curing, for example, it can be carried out at 100°C or higher and 200°C or lower, preferably 120°C or higher and 180°C or lower, more preferably 140°C or higher and 160°C or lower. It should be noted that the heating time in the first stage is, for example, about 5 minutes or more and 20 hours or less, preferably about 30 minutes or more and 12 hours or less. In addition, the heating time in the second stage and later is, for example, about 10 minutes or more and 15 hours or less, preferably 1 hour or more and 10 hours or less.

[0227] By heating the molded body obtained from the mixed composition in the first stage at a relatively low temperature as described above, the volatile substance is not easily foamed to generate large bubbles, and in addition, the molded body can be cured in such a way that the volatile substance remains in the molded body.

[0228] In addition, when the molded body is sliced and heated in the second stage at a relatively high temperature, since the molded body is cured, it will not foam to generate large bubbles even at high temperatures, and the space where the volatile substances exist becomes fine bubbles. The size of the above-mentioned bubbles is, for example, 1 μm or less, preferably 0.2 μm or less. In addition, the lower limit of the bubble size is not particularly limited, for example, it is 0.001 μm or more.

[0229] In Step 2, the mixed composition can be molded into a prescribed shape such as a block or a sheet, and heated to cure it. In addition, in Step 2, when the mixed composition contains an anisotropic filler as a heat-conductive filler, it can be cured by heating on the basis of orienting the anisotropic filler in one direction. The anisotropic filler can be oriented by a magnetic field orientation method or a flow orientation method, and preferably by a magnetic field orientation method.

[0230] In the magnetic field orientation method, after injecting the mixed composition into the inside of a mold or the like, it is placed in a magnetic field to orient the anisotropic filler along the magnetic field. Then, an oriented molded body can be obtained by curing the curable polymer composition. The curing of the mixed composition can be carried out under the heating conditions as described above.

[0231] As the oriented molded body, a block shape is preferred, but a sheet shape is also possible. By forming it into a sheet shape, the oriented molded body can be directly coated with an adhesive in Step 3 without slicing. On the other hand, by molding it into a block shape, the orientation of the anisotropic filler is improved.

[0232] In the magnetic field orientation method, a release film can be disposed at a portion in contact with the mixed composition inside the mold. For the release film, for example, a resin film with good releasability, a resin film that has been subjected to a release treatment such as a single-sided release agent, etc. is used. By using the release film, the oriented molded body is easily demolded from the mold.

[0233] For magnetic field orientation, the viscosity of the mixed composition used in the magnetic field orientation method is preferably 50 Pa·s or more and 1500 Pa·s or less. By setting it to 50 Pa·s or more, the heat-conductive filler is not likely to settle. In addition, by setting it to 1500 Pa·s or less, the fluidity becomes good, the anisotropic filler is properly oriented in the magnetic field, and there will be no adverse situation where the orientation takes too much time. It should be noted that the viscosity refers to the viscosity measured at a rotational speed of 5 rpm at 25 °C using a rotational viscometer (Brookfield viscometer DV-E, rotor SC4-14).

[0234] However, in the case of using a heat-conductive filler that is difficult to settle or combining additives such as an anti-settling agent, the viscosity of the mixed composition can be less than 50 Pa·s.

[0235] In the magnetic field orientation method, as a magnetic field generation source for applying magnetic field lines, superconducting magnets, permanent magnets, electromagnets, etc. can be cited. Considering from the aspect of generating a magnetic field with a high magnetic flux density, a superconducting magnet is preferred. The magnetic flux density of the magnetic field generated from these magnetic field generation sources is preferably 1 to 30 teslas. If the magnetic flux density is set to 1 tesla or more, the above-mentioned anisotropic fillers made of carbon materials, etc. can be easily oriented. In addition, by setting it to 30 teslas or less, actual manufacturing can be carried out.

[0236] In the flow orientation method, a shearing force is applied to the mixed composition to manufacture a primary sheet in which the anisotropic fillers are oriented in the plane direction. More specifically, in the flow orientation method, first, while applying a shearing force to the mixed composition prepared in Step 1, it is flattened and elongated and formed into a sheet (primary sheet). By applying the shearing force, the anisotropic fillers can be oriented in the shearing direction. As a means for forming the sheet, for example, the mixed composition can be coated on a substrate film by a coating applicator such as a bar coater or a doctor blade, or by extrusion molding, spraying from a nozzle, etc., and then dried as needed, or the mixed composition can be semi-cured, or completely cured. The thickness of the primary sheet is preferably set to about 50 μm or more and 5000 μm or less. In the primary sheet, the anisotropic fillers are oriented in one direction along the plane direction of the sheet.

[0237] The mixed composition used in the flow orientation method has a relatively high viscosity so that a shearing force is applied when it is elongated into a sheet. Specifically, for the viscosity of the mixed composition, it is preferably 3 Pa·s or more and 500 Pa·s or less.

[0238] The primary sheet can also be used directly as a heat-conducting sheet without being made into a block as described later. In addition, multiple primary sheets can be overlapped and laminated in the same orientation direction, and then, as needed, while curing them by heating, the primary sheets can be bonded to each other by hot pressing, etc., thereby forming a laminated block (block-shaped orientation molded body).

[0239] In addition, in the case of forming a laminated block, at least one of the mutually overlapping surfaces of the primary sheets can be irradiated with vacuum ultraviolet rays and then the primary sheets can be overlapped. When the primary sheets are overlapped by means of the surfaces irradiated with vacuum ultraviolet rays, the primary sheets can be firmly bonded to each other. In addition, in the case of irradiating with vacuum ultraviolet rays, the mixed composition can be completely cured when manufacturing the primary sheets, and it is not necessary to cure them by heating, etc. when overlapping the primary sheets to form a laminated block.

[0240] In the flow orientation method, the curing of the mixed composition can also be carried out under the heating conditions as described above.

[0241] As described above, when forming a block-shaped oriented molded body, the obtained oriented molded body can be cut by slicing or the like perpendicular to the direction in which the oriented molded body is oriented with respect to the anisotropic filler to form a sheet-shaped molded body. For slicing, for example, a shear knife, a laser, or the like can be used. For the sheet-shaped molded body, sometimes a part of the fibrous filler is exposed from the matrix on each surface serving as a cut surface due to cutting such as slicing. The exposed fibrous filler hardly falls down and is oriented in the thickness direction.

[0242] However, in Step 2, as the oriented molded body is cut by slicing or the like, the fibrous filler contained in the oriented molded body can also be cut within a range that does not impair the effects of the present invention.

[0243] The sheet-shaped molded body obtained by cutting can be directly coated with an adhesive in Step 3 described below, or can be further subjected to other treatments. For example, each surface serving as a cut surface can also be polished. In addition, as described above, secondary curing can be performed. It should be noted that secondary curing can be performed after polishing or before polishing.

[0244] For the sheet-shaped molded body, by being polished, the surface state of the sheet-shaped molded body becomes better, and it is easier to further reduce the thermal resistance value. For the sheet-shaped molded body, by being polished, the surface of the sheet can be smoothed in a state where a certain amount of anisotropic fillers such as fibrous fillers are exposed on the surface. In addition, the fibrous fillers can also be in a fallen state or the like. Therefore, it is easy to make the surface of the heat-conducting sheet fit tightly with other members, and in addition, it is easy to form a state where a certain area or more of the sheet surface is covered with fibrous fillers, and it is easy to reduce the thermal resistance value.

[0245] Regarding polishing, at least one surface of the obtained sheet-shaped molded body can be polished, but it is preferable to polish both surfaces of the sheet-shaped molded body. For surface polishing, for example, sandpaper, a polishing film, a polishing cloth, a polishing belt, or the like can be used.

[0246] As the properties of the sandpaper, the average particle diameter (D50) of the abrasive grains contained is preferably 0.1 μm or more and 100 μm or less, more preferably 1 μm or more and 60 μm or less. In addition, as the abrasive grain size of the sandpaper, it is preferably #120 to 20000, preferably #300 to 15000, more preferably #320 to 4000.

[0247] For the polishing method, in addition to polishing by continuously abutting the sandpaper in the same straight-line direction with respect to the surface of the sheet-shaped molded body, methods such as reciprocating a certain distance for polishing, or rotating in the same direction for polishing, or abutting in various directions for polishing can also be used.

[0248] In addition, regarding the degree of polishing, for example, it can be carried out while observing the surface state. For example, in the case of reciprocating polishing, preferably 1 or more and 300 or less reciprocations, more preferably 3 or more and 250 or less, and still more preferably 5 or more and 100 or less.

[0249] The surface polishing of the sheet-shaped molded body can be carried out in two polishing steps. For example, the first polishing can be carried out using abrasive paper with a relatively large average particle diameter of abrasive grains, and then the second polishing can be carried out using abrasive paper with a smaller average particle diameter of abrasive grains than that in the first polishing.

[0250] (Process 3)

[0251] In Process 3, an adhesive is applied to the surface of the cured product such as the sheet-shaped molded body obtained in Process 2 as described above.

[0252] In addition, in this manufacturing method, it is preferable to allow the adhesive to penetrate into the heat-conducting layer, but it is preferable to allow the adhesive to penetrate into the interior of the heat-conducting layer only by applying the adhesive.

[0253] The adhesive can be diluted with a diluent and applied as an adhesive diluent to the surface of the sheet-shaped molded body. By diluting the adhesive with a diluent, it is easy for the adhesive to penetrate into the heat-conducting layer. As the diluent, there is no particular limitation as long as it is a liquid at 25°C and 1 atmosphere, has solubility or compatibility with the adhesive, and volatilizes by drying described later, and an organic solvent can be preferably used.

[0254] There is no particular limitation on the organic solvent used, and examples thereof include ketone compounds such as acetone, methyl ethyl ketone, and cyclohexanone; aromatic hydrocarbon compounds such as toluene, xylene, and tetramethylbenzene; cellosolves, methyl cellosolves, butyl cellosolves, carbitols, methyl carbitols, butyl carbitols, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, tripropylene glycol monomethyl ether, polyethylene glycol monomethyl ether, and polyethylene glycol monoethyl ether; ester compounds such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate; and aliphatic hydrocarbon compounds such as hexane, octane, and decane.

[0255] It should be noted that from the aspect of spraying described later to appropriately penetrate the adhesive into the heat-conducting layer, it is preferable to include any one of cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, and polyethylene glycol monoethyl ether as the organic solvent.

[0256] In addition, besides the above-mentioned organic solvents, it is preferably further contained with organic solvents having a boiling point lower than theirs. Specifically, methyl ethyl ketone, methyl isobutyl ketone, hexane, ethyl acetate, butyl acetate, toluene, etc. can be cited.

[0257] The dilution concentration using the diluent is not particularly limited, and it can be adjusted in such a manner that the solid content concentration of the adhesive becomes, for example, 5% by mass or more and 50% by mass or less, preferably 8% by mass or more and 35% by mass or less, and more preferably 10% by mass or more and 25% by mass or less. If the solid content concentration is set to 5% by mass or more, it is possible to prevent overheating during drying more than necessary, and it is possible to appropriately infiltrate a specified amount of the adhesive together with the organic solvent into the heat conductive layer. In addition, by setting it to 50% by mass or less, the weight per unit area is not too large, and in addition, the viscosity can be adjusted to an easily infiltrating viscosity, so that the adhesive can appropriately infiltrate into the heat conductive layer. Moreover, by setting the dilution concentration within the above range, it is easy to adjust the amount of volatile components at 150°C and 260°C to a specified range.

[0258] It should be noted that the amount of the adhesive infiltrating into the heat conductive layer can be adjusted according to the viscosity, solid content concentration, type of solvent, etc. For example, when it is desired to increase the amount of the infiltrating adhesive, the solid content concentration can be adjusted from a low viscosity to a high concentration. In addition, when it is desired to reduce the amount of the infiltrating adhesive material, it is only necessary to set the solid content concentration to a low concentration with a high viscosity.

[0259] The coating method of the adhesive is not particularly limited, and a known coating method can be adopted, preferably spraying. By performing spraying, the weight per unit area is not too large, and in addition, it is easy to appropriately infiltrate the adhesive into the heat conductive layer. In addition, by spraying and suppressing the coating amount, it is also possible to provide a portion with an adhesive layer and a portion without an adhesive layer on the surface of the heat conductive layer. It should be noted that in the case of spraying, it is preferable to spray an adhesive containing a quick-drying organic solvent such as ethyl acetate and a slow-drying organic solvent such as polyethylene glycol monoethyl ether and propylene glycol monomethyl ether acetate. More specifically, by containing a slow-drying organic solvent, when the adhesive sprayed from the sprayer is coated on the surface of the heat conductive layer, the organic solvent does not volatilize excessively, and thus the adhesive easily infiltrates into the heat conductive layer. On the other hand, it is preferably adjusted to a viscosity suitable for spraying by containing a quick-drying solvent.

[0260] For the coated adhesive, the diluent can be volatilized by subsequent drying. Considering that the volatile component amount at 150°C is below a certain amount and it is easy to achieve good adhesion after high-temperature heating such as in the reflow soldering process, the drying temperature is preferably 60°C or higher, more preferably 70°C or higher, and further preferably 80°C or higher. Additionally, considering that the volatile component amount at 150°C is above a certain amount and it is easy to achieve good initial adhesion, the drying temperature is preferably 170°C or lower, more preferably 150°C or lower, and further preferably 120°C or lower.

[0261] Regarding the drying time, it only needs to be a time when substantially all of the diluent contained in the coated adhesive has volatilized. Considering that the volatile component amount at 150°C is below a certain amount and it is easy to achieve good adhesion after high-temperature heating such as in the reflow soldering process, it is preferably 10 minutes or longer, more preferably 20 minutes or longer, and further preferably 30 minutes or longer. Additionally, considering that the volatile component amount at 150°C is above a certain amount and it is easy to achieve good initial adhesion, the drying time is preferably 30 hours or shorter, more preferably 6 hours or shorter, and further preferably 3 hours or shorter.

[0262] In addition, the above drying can be carried out at normal pressure, or it can be vacuum drying or reduced-pressure drying carried out under reduced pressure. In reduced-pressure or vacuum drying, the drying temperature can be appropriately lowered or the drying time can be appropriately shortened.

[0263] It should be noted that the above manufacturing method is an example, and the heat sink does not necessarily need to be manufactured by the above manufacturing method. For example, it can be manufactured by a method that omits the above step 3. In this case, the heat sink does not have an adhesive layer, and as long as the adhesive is included in the heat-conducting layer. Also, the heat-conducting layer containing the adhesive can be used as the heat sink, or it can be disposed on the surface of the heat sink so that at least one surface of the heat sink has adhesiveness. In this case, the adhesive can be incorporated into the mixed composition in step 1.

[0264] As described above for the adhesive contained in the heat-conducting layer, detailed description is omitted. In the case of omitting the above step 3 and including the adhesive in the heat-conducting layer, in step 1, the adhesive can be appropriately mixed with the above curable polymer composition, heat-conducting filler, volatile substances added as needed, and other components added optionally as needed in any order.

[0265] It should be noted that when the adhesive is incorporated into the mixed composition in Step 1, the adhesive can be diluted with a diluent and incorporated into the mixed composition in the form of an adhesive diluent, or it can be incorporated into the mixed composition without being diluted with a diluent. Regarding the diluent, as described above, detailed description is omitted. Additionally, when the adhesive diluent is incorporated into the mixed composition, the diluent can volatilize during heating in Step 2 above.

[0266] [Use of the heat-conducting sheet]

[0267] The heat-conducting sheet is inserted between the heat-generating body and the heat-dissipating body, conducts the heat released by the heat-generating body and moves it to the heat-dissipating body, and dissipates heat from the heat-dissipating body. The heat-conducting sheet is used in electronic device applications, semiconductor applications, etc., and is preferably used in semiconductor applications. In semiconductor applications, the heat-conducting sheet can be used in any application, and is preferably used in applications such as those called TIM1 that are directly applied to semiconductor chips such as silicon chips. For example, it is preferably used between a semiconductor chip and a radiator.

[0268] Of course, it can also be used in applications such as those called TIM2 that are not directly applied to semiconductor chips. In this case, the heat-conducting sheet can be used, for example, between a radiator and other cooling units such as a radiator, a heat pipe.

[0269] In addition, for the heat-conducting sheet, in addition to the above, it can also be used between various electronic components that become heat-generating bodies and heat-dissipating bodies such as radiators, heat pipes, heat pumps, and the metal housing of electronic devices.

[0270] In addition, the heat-conducting sheet is also preferably used in the semiconductor inspection process for inspecting semiconductor components such as semiconductor packages. Especially in the semiconductor inspection process, it is preferably used between the test head and the semiconductor package.

[0271] The heat-conducting sheet can be configured to be used between two components (adherends) such as a heat-dissipating body and a heat-generating body, and can be used in a state of being closely adhered to and compressed with each component (adherend).

[0272] The heat-conducting sheet can be laminated on the adherend at room temperature, or as described later, it can be laminated on the adherend by heating to an appropriate temperature, thereby being installed on the adherend.

[0273] In addition, the heat-conducting sheet can be used in the form of a laminate having a metal foil such as aluminum foil adhered to at least one surface. The laminate can be formed by adhering a metal foil to the heat-conducting sheet of the present invention having adhesiveness on the surface, and the heat-conducting sheet is obtained by coating an adhesive on one surface of the heat-conducting sheet to form an adhesive layer or the like. In addition, an adhesive can also be coated on the surface of the metal foil, and the metal foil can be adhered to the heat-conducting sheet on which the adhesive is not coated, thereby laminating the metal foil while manufacturing the heat-conducting sheet of the present invention. In addition, when laminating the metal foil only on one surface of the heat-conducting sheet, an adhesive can be coated on the other surface of the heat-conducting sheet, or the adhesive can not be coated, but from the aspect of improving the adhesion of the two surfaces of the heat-conducting sheet to the adherend, it is preferable to also coat an adhesive on the other surface of the heat-conducting sheet to form an adhesive layer.

[0274] As Figure 1 shown, sometimes an adhesive 11 used for fixing the LID 10 used in a semiconductor package or the like during installation is coated near the heat-conducting sheet 12. In this case, when the heat-conducting sheet 12 is mounted on an adherend 13 such as an IC chip, the structure 1 including the LID 10, the adhesive 11, the heat-conducting sheet 12, and the adherend 13 can be heated. By performing this heating, the adhesive of the adhesive 11 can be cured, and before the reflow soldering process, the LID 10 can be fixed to the substrate 14 on which the IC chip or the like is mounted by means of the adhesive 11. It should be noted that the component for fixing the LID 10 to the substrate is not limited to the adhesive 11, and it can also be a sealing material or the like. For example, in the case of using a sealing material, the sealing material can be adhered to the substrate 14, and the adhesive of the sealing material can be cured by the above heating, and the LID 10 can be fixed to the substrate by means of the sealing material.

[0275] Thus, the deviation of the LID 10 or the like during the reflow soldering process can be suppressed. In addition, during heating, the heat-conducting sheet 12 can be appropriately pressed and laminated on the adherend 13 by thermocompression bonding. In addition, the heat-conducting sheet 12 can be adhered to the adherend 13 by means of at least one surface of the adhesive heat-conducting layer.

[0276] In addition, for the heating temperature during installation, it is sufficient that the temperature is lower than the temperature during the high-temperature heating described later. For example, it is about 100 to 200 °C, and preferably about 120 to 170 °C. Since the amount of volatile components of the heat-conducting sheet at 150 °C is small, it is possible to prevent the adhesion of the heat-conducting sheet to the adherend from being reduced due to the heating during installation.

[0277] In addition, the thermally conductive sheet is preferably used in applications where it is heated to a high temperature of, for example, 200° C. to 300° C., preferably 220° C. to 270° C., in a state where at least one surface of the thermally conductive sheet is in close contact with an adherend via an adhesive thermally conductive layer. The thermally conductive sheet of the present invention can prevent the adhesive force to the adherend from decreasing as described above even when heated at a high temperature in a state where the sheet is in close contact with the adherend, and thus can prevent the sheet from peeling off from the adherend even when heated to a high temperature.

[0278] For semiconductor applications, the thermally conductive sheet can be installed in a manner that forms a state of being closely attached to an adherend such as a substrate or a silicon wafer. Furthermore, the thermally conductive sheet is preferably provided to the reflow process in a state of being closely attached to the adherend, and can be heated within the above-mentioned high temperature range in the reflow process. It should be noted that, for the thermally conductive sheet, for example, a semiconductor chip or a thermal sprayer can be used as an adherend, and heated through the reflow process in a state of being closely attached to one or both of them.

[0279] Example

[0280] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0281] The measuring method and the evaluation method in this example are as follows.

[0282] [Sheet thickness]

[0283] The thickness (initial thickness) of the thermally conductive sheet was measured using a thickness gauge.

[0284] [stickiness value]

[0285] The adhesion tester TA-500 manufactured by UBM was used, and the thermal conductive sheet was fixed on a workbench with double-sided tape, and the maximum load measured under the following measurement conditions was taken as the adhesion value (N). The double-sided tape used was "Nestack NW-K15" manufactured by Nichiban.

[0286] (Measurement conditions)

[0287] Probe diameter: 5mmφ Pressing load: 20N

[0288] Holding time: 10 seconds Pulling speed: 0.1mm / s

[0289] Measurement environment: 23°C, 50% RH

[0290] [Volatile content at 150°C]

[0291] In order to determine the residual solvent in the sample, measurement was performed using thermal desorption GC-MS under the following conditions.

[0292] <Thermal Desorption GC-MS Determination Conditions>

[0293] Thermal desorption device: TurboMatrix 350

[0294] Sample amount: 5 mg accurately weighed

[0295] Heating: 150 °C, 10 min (20 mL / min)

[0296] Secondary desorption: 350 °C

[0297] Split flow: inlet 25 mL / min, outlet 25 mL / min, injection volume 2.5%

[0298] GC-MS device: Agilent 7890B & JMS-Q1500GC (manufactured by JEOL Ltd.)

[0299] Column: EQUITY-1 (non-polar) 0.32 mm × 60 m × 0.25 μm

[0300] GC temperature increase: 40 °C (4 min) → 300 °C (10 min) (heating at a rate of 10 °C / min)

[0301] He flow rate: 1.5 mL / min (split ratio 1:30)

[0302] Ionization voltage: 70 eV

[0303] MS measurement range: 29 - 600 amu (scan 500 ms)

[0304] MS temperature: ion source 230 °C, interface 250 °C

[0305] Quantification is calculated using the peak area of toluene when measuring a 2 μL methanol solution adsorbed with 100 ppm toluene concentration in a Tenax tube under the same conditions as the sample.

[0306] [Amount of volatile components at 260 °C]

[0307] To determine the residual solvent in the sample, measurement is performed using thermal desorption GC-MS under the following conditions. The measurement of the amount of volatile components at 260 °C is evaluated using the sample after measuring the amount of volatile components at 150 °C.

[0308] <Thermal Desorption GC-MS Determination Conditions>

[0309] Thermal desorption device: TurboMatrix 350 (PerkinElmer)

[0310] Sample amount: 5 mg accurately weighed

[0311] Heating: 260 °C, 5 min (20 mL / min)

[0312] Secondary desorption: 350 °C

[0313] Split flow: inlet 25 mL / min, outlet 25 mL / min, injection volume 2.5%

[0314] GC-MS device: Agilent 7890B & JMS-Q1500GC (manufactured by JEOL Ltd.)

[0315] Column: EQUITY-1 (non-polar) 0.32 mm × 60 m × 0.25 μm

[0316] GC temperature programming: 40 °C (4 min) → 300 °C (10 min) (heating at a rate of 10 °C / min)

[0317] He flow rate: 1.5 mL / min (split ratio 1:30)

[0318] Ionization voltage: 70 eV

[0319] MS measurement range: 29 - 600 amu (scan 500 ms)

[0320] MS temperature: ion source 230 °C, interface 250 °C

[0321] Quantification is performed by calculating using the peak area of toluene when measuring a 2 μL methanol solution adsorbed with 100 ppm toluene concentration in a Tenax tube under the same conditions as the sample.

[0322] [SAT coverage rate]

[0323] The SAT coverage rate based on thermal pressing is obtained through the following steps 1. to 3.

[0324] 1. Prepare a 30 mm square copper plate and a silicon wafer, sandwich the heat conducting sheet obtained in each example and comparative example between the copper plate and the silicon wafer, place a heavy object on the copper plate, and press at 150 °C for 10 minutes under a pressure of 30 psi to obtain a SAT sample.

[0325] 2. Using the sample obtained in 1. above, perform ultrasonic flaw detection inspection (SAT) to obtain an observation image of the heat conducting sheet. SAT is performed using a high-precision ultrasonic inspection device ("C-SAM D9500" manufactured by Nippon Burns Co., Ltd.).

[0326] 3. Binarize the image obtained in 2. above using the image processing software ImageJ under the condition of a brightness value of 251. Capture the colored part in the image as the bonded part, and obtain the ratio of the bonded part to the total area as the SAT coverage rate based on thermocompression bonding. It should be noted that in ultrasonic flaw detection, the SAT coverage rate at the interface between the copper plate and the heat sink is calculated.

[0327] In addition, regarding the SAT coverage rate after high-temperature heating, the sample obtained in 1. above is further heated at 260 °C for 3 minutes, and the SAT coverage rate is obtained using the methods in 2. and 3. as the SAT coverage rate after high-temperature heating. The heating at 260 °C for 3 minutes is carried out in a reflow soldering furnace (manufactured by Antum Corporation, "UNI-5016F") in the same way as the reflow soldering process.

[0328] The following components are used as raw materials for the heat sink.

[0329] (Main agent and curing agent)

[0330] Curable silicone: An addition reaction type organopolysiloxane composed of an alkenyl-containing organopolysiloxane as the main agent and a hydrogen organopolysiloxane as the curing agent (including a catalytic amount of platinum catalyst).

[0331] (Volatile substances)

[0332] n-Decyltrimethoxysilane

[0333] (Thermal conductive filler)

[0334] Aluminum oxide 1: Polyhedral shape, average particle size (D50) = 0.5 μm, aspect ratio 1.0

[0335] Aluminum oxide 2: Polyhedral shape, average particle size (D50) = 3.0 μm, aspect ratio 1.0

[0336] Aluminum: Spherical shape, average particle size (D50) = 3 μm, aspect ratio 1.0 - 1.5

[0337] Graphitized carbon fiber: Average fiber length (arithmetic mean) 85 μm, diameter 10 μm, aspect ratio 8.5, thermal conductivity 900 W / m·K

[0338] Flake graphite powder: Average particle size (D50) = 15 μm, aspect ratio 10, thermal conductivity 550 W / m·K

[0339] (Polymer dispersant)

[0340] Pyrene dispersant: An organopolysiloxane having pyrene as shown in the synthesis method described later, number average molecular weight 17000

[0341] (Synthesis of pyrene dispersant)

[0342] 98.6 g of an organosiloxane compound (n=210) having a 1,3-diol group, 1.4 g of 1-pyrene carboxaldehyde, 50 g of toluene as a solvent, and 0.6 g of a catalyst (Amberlyst 15dry, manufactured by Olgano Co., Ltd.) were reacted at 100°C for 24 hours under a nitrogen atmosphere. After the reaction, the catalyst was removed by filtering with a 5.0 μm PTFE filter, and the filtrate was concentrated with a rotary evaporator and a vacuum dryer to obtain a pyrene dispersant 1. If the reaction formula is shown, it is as follows. It should be noted that by 1 H NMR measurement confirmed the following reaction proceeding. As the NMR measuring apparatus, "ECX-400" manufactured by JEOL was used, deuterated chloroform was used as the solvent, and the measurement was performed under the conditions of sample concentration 1 wt%, 25°C, measuring frequency 400 MHz, and accumulation times 8 times.

[0343]

[0344] (Adhesive)

[0345] The adhesive main agent is an acrylic polymer having a structural unit derived from 2-ethylhexyl acrylate as a main component and having a hydroxyl group, a carboxyl group, and a vinyl group on the side chain.

[0346] ※It should be noted that 100 parts by mass of a dilution solution of an adhesive diluted with ethyl acetate to a solid concentration of 33% by mass was further diluted with 150 parts by mass of propylene glycol monomethyl ether acetate (solvent) to prepare a coating solution with a solid concentration of 13.2% by mass, which was used in each of the Examples and Comparative Examples.

[0347] [Example 1]

[0348] According to the formulation in Table 1, the components were mixed at 25°C for 50 minutes using a planetary mixer to obtain a mixed composition. Next, the mixed composition was injected into a mold having a thickness set to be sufficiently larger than the thermal conductive sheet, and an 8T magnetic field was applied in the thickness direction to orient the carbon fibers and flake graphite in the thickness direction, and then heated at 80°C for 8 hours to cure the curable silicone once, thereby obtaining a block-shaped oriented molded body.

[0349] Next, the block-shaped oriented molded body was sliced ​​into sheets with a thickness of 100 μm using a shear knife, thereby obtaining a sheet-shaped molded body with exposed carbon fibers. The sheet-shaped molded body was then heated at 150° C. for 6 hours for secondary curing.

[0350] Next, the sheet-shaped molded body was polished reciprocally 75 times using a coarse-grit polishing paper A (grain size #800) with an average abrasive grain diameter (D50) of 20 μm, and then further polished reciprocally 10 times using a coarse-grit polishing paper B (grain size #4000) with an average abrasive grain diameter (D50) of 3 μm.

[0351] Table 1

[0352] Each component Formulation Curable silicone 100 n-Decyltrimethoxysilane 15 Aluminum oxide 1 30 Aluminum 243 Graphitized carbon fiber 160 Flake graphite powder 20 Sheet hardness 59

[0353] ※ The values of the respective components in Table 1 are parts by mass.

[0354] ※ The sheet hardness is the E-type hardness measured for the cured product obtained from the above formulation in each of the examples and comparative examples.

[0355] On both surfaces of the obtained sheet-shaped molded body, an adhesive coating liquid was sprayed while adjusting the discharge amount so that the unit area weight after drying became the amount described in Table 5, and then it was dried under the drying conditions described in Table 5, thereby obtaining a heat-conducting sheet having an acrylic adhesive layer provided on both surfaces of the heat-conducting layer (sheet-shaped molded body).

[0356] [Examples 2 and 4]

[0357] Except for changing the unit area weight or drying conditions as shown in Table 5, a heat-conducting sheet having an acrylic adhesive layer provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0358] [Example 3]

[0359] Except for changing the material of the block-shaped oriented molded body to the formulation in Table 2, a heat-conducting sheet having an acrylic adhesive layer provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0360] Table 2

[0361] Each component Formulation Curable silicone 100 n-Decyltrimethoxysilane 3 Pyrene dispersant 10 Aluminum oxide 1 30 Aluminum oxide 2 300 Graphitized carbon fiber 160 Flake graphite powder 20 Sheet hardness 40

[0362] ※ The values of the respective components in Table 2 are parts by mass.

[0363] ※ The sheet hardness is the E-type hardness measured for the cured product obtained from the above formulation in Example 3.

[0364] [Example 5]

[0365] Except for slicing the block-shaped oriented molded body into sheets with a thickness of 200 μm, a heat-conducting sheet having an acrylic adhesive layer provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0366] [Example 6]

[0367] Change the material of the block-shaped oriented molded body to the formulation in Table 3, change the drying conditions as in Table 6, and spray the coating liquid of the adhesive only on one side of the obtained sheet-shaped molded body. Other than that, obtain a heat-conducting sheet having an acrylic adhesive layer provided on one surface of the heat-conducting layer according to the same procedure as in Example 1.

[0368] Table 3

[0369] Each component Formulation Curable silicone 100 n-Decyltrimethoxysilane 3 Pyrene dispersant 10 Aluminum oxide 1 30 Aluminum oxide 2 300 Graphitized carbon fiber 160 Flake graphite powder 20 Sheet hardness 60

[0370] ※ The values of each component in Table 3 are in parts by mass.

[0371] ※ The sheet hardness is the E-type hardness measured for the cured product obtained from the above formulation in Example 6.

[0372] [Example 7]

[0373] Except for slicing the block-shaped oriented molded body into sheets with a thickness of 200 μm, obtain a heat-conducting sheet having an acrylic adhesive layer provided on one surface of the heat-conducting layer according to the same procedure as in Example 6.

[0374] [Example 8]

[0375] Except for slicing the block-shaped oriented molded body into sheets with a thickness of 200 μm and changing the weight per unit area as in Table 6, obtain a heat-conducting sheet having an acrylic adhesive layer provided on one surface of the heat-conducting layer according to the same procedure as in Example 6.

[0376] [Example 9]

[0377] Except for slicing the block-shaped oriented molded body into sheets with a thickness of 400 μm, obtain a heat-conducting sheet having an acrylic adhesive layer provided on one surface of the heat-conducting layer according to the same procedure as in Example 6.

[0378] [Example 10]

[0379] Change the material of the block-shaped oriented molded body to the formulation in Table 4. As an alternative to providing an adhesive layer, make the heat-conducting layer contain an adhesive and do not perform spraying. Other than that, obtain a heat-conducting sheet having adhesiveness on both surfaces of the heat-conducting layer according to the same procedure as in Example 1. It should be noted that the adhesive used in Example 10 is the same as the adhesives used in other examples and comparative examples except that it is not diluted with various diluents.

[0380] Table 4

[0381] Each component Formulation Curable silicone 100 n-Decyltrimethoxysilane 5 Pyrene dispersant 10 Acrylic adhesive 10 Aluminum oxide 1 30 Aluminum oxide 2 300 Graphitized carbon fiber 160 Flake graphite powder 20 Sheet hardness 40

[0382] ※ The values of each component in Table 4 are in parts by mass.

[0383] ※ The sheet hardness was the E-type hardness measured for the heat-conducting sheet obtained in Example 10.

[0384] [Comparative Example 1]

[0385] Except for changing the drying conditions and the weight per unit area as shown in Table 7, a heat-conducting sheet having acrylic adhesive layers provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0386] [Comparative Example 2]

[0387] Except for changing the drying conditions as shown in Table 7, a heat-conducting sheet having acrylic adhesive layers provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0388] [Comparative Example 3]

[0389] Except for not coating the adhesive coating liquid on both surfaces of the sheet-shaped molded body, a heat-conducting sheet having no acrylic adhesive layers provided on both surfaces of the heat-conducting layer was obtained according to the same procedure as in Example 1.

[0390] Table 5

[0391]

[0392] Table 6

[0393]

[0394] Table 7

[0395] Comparative Example 1 Comparative Example 2 Comparative Example 3 Type of sheet Sheet 1 Sheet 1 Sheet 1 Sheet thickness 100 μm 100 μm 100 μm Coating surface Both sides Both sides - <![CDATA[Grammage (mg / cm 2 )]]> 0.70 0.34 - Drying conditions 50 °C 5 min 100 °C 180 min - Viscosity value (N) 7.66 3.21 1.92 Amount of volatile components at 150 °C 136 mass ppm 0 mass ppm 0 mass ppm SAT coverage based on thermal lamination 71% 57% 58% Amount of volatile components at 260 °C 2823 mass ppm 450 mass ppm 1059 mass ppm SAT coverage after high-temperature heating 57% 52% 57%

[0396] ※ In Tables 5 to 7, "type of sheet" refers to the type of heat-conducting layer with different formulations. Specifically, "sheet 1" refers to the heat-conducting layer obtained from the formulation in Table 1, "sheet 2" refers to the heat-conducting layer obtained from the formulation in Table 2, "sheet 3" refers to the heat-conducting layer obtained from the formulation in Table 3, and "sheet 4" refers to the heat-conducting layer obtained from the formulation in Table 4.

[0397] From the above results, it can be seen that for the heat-conducting sheets produced in each example, since the amount of volatile components at 150 °C is within a certain range, the SAT coverage rate as an index of adhesion becomes higher before and after the reflow soldering process accompanied by high-temperature heating.

[0398] In contrast, for the heat conductive sheet produced in Comparative Example 1, since the amount of volatile components at 150°C was excessive, the SAT coverage rate decreased significantly after the reflow soldering process. In addition, for the heat conductive sheet produced in Comparative Example 2, since the amount of volatile components at 150°C was too small, not only the SAT coverage rate was low after the reflow soldering process, but also the SAT coverage rate was low before the reflow soldering process. That is, excellent initial adhesion could not be obtained. In addition, for the heat conductive sheet produced in Comparative Example 3, since the adhesive coating liquid was not applied, excellent initial adhesion was not obtained as in Comparative Example 2.

[0399] Symbol description

[0400] 1 Structure

[0401] 10LID

[0402] 11 Adhesive

[0403] 12 Heat conductive sheet

[0404] 13 Adherend

[0405] 14 Substrate

Claims

1. A thermally conductive sheet comprising a thermally conductive layer comprising a polymer matrix and a thermally conductive filler, wherein at least one surface of the thermally conductive sheet is adhesive, wherein the amount of volatile components measured by thermal desorption GC-MS at 150° C. is 2 mass ppm or more and 80 mass ppm or less. The thermally conductive sheet according to claim 1 , wherein the polymer matrix is ​​organic polysiloxane. 3 . The thermally conductive sheet according to claim 1 , further comprising an adhesive layer on at least one surface of the thermally conductive layer. The thermally conductive sheet according to claim 3 , wherein the adhesive layer is formed by spraying. The thermally conductive sheet according to claim 3 , wherein the adhesive layer is an acrylic adhesive layer. The thermally conductive sheet according to claim 5 , wherein the acrylic adhesive layer has a reactive double bond. 7 . The thermally conductive sheet according to claim 1 , wherein the adhesiveness disappears by heating at 260° C. for 3 minutes. 8 . The thermally conductive sheet according to claim 1 , wherein the amount of volatile components measured by thermal desorption GC-MS at 260° C. is 2500 mass ppm or less. 9 . The thermally conductive sheet according to claim 1 , wherein the adhesive force of the at least one surface measured by a tack test is 2 N or more.

10. A thermally conductive sheet comprising a thermally conductive layer comprising a polymer matrix and a thermally conductive filler, wherein at least one surface of the thermally conductive layer is adhesive, and the amount of volatile components of the thermally conductive sheet measured by thermal desorption GC-MS at 150°C is 2 mass ppm or more and 80 mass ppm or less.

Citation Information

Patent Citations

  • Thermally conductive sheet, and method for producing thermally conductive sheet

    JP2020116874A